Synthesis and curing studies of PPG based telechelic urethane methacrylic macromonomers - Asha, S. K.; Thirumal, M.; Kavitha, A.; Pillai, C.K.S. (European Polymer Journal, 2005)
A New class of telechelic urethane methacrylic (TUMA) macromonomers were synthesized by a two-step condensation of 1, 6-hexamethylenediisocyanate (HMDI) with polypropylene glycol (PPG) of various molecular weights and capped with hydroxyl ethyl methacrylate (HEMA). A model compound based on diethylene glycol (DEG)—M-1 was synthesized as a low molecular weight analogue. Another model compound—M-2 was also synthesized by direct coupling of two equivalents of HEMA with HMDI. The structure of the telechelic urethanes were confirmed by 1H, 13C NMR and FTIR spectroscopy. Photopolymerization of these telechelic systems was investigated using 2,2-diethoxy acetophenone as the photoinitiator at 5 wt.%. Trihydroxymethylpropane trimethacrylate (30 parts), PPG diacrylates (25 parts), ethylhexyl acrylate (20 parts) were mixed with the various telechelic urethane methacrylates (25 parts) for curing studies. The kinetics of the curing was monitored by following the disappearance of the methacrylic double bonds at 1628 cm−1 using IR spectroscopy. TUMAPPG-425 had the fastest cure rate among the telechelic urethane methacrylates. This could be accounted for by hydrogen bonding pre-association in these systems. The thermal properties of the cured films were studied using TGA measurements. The cured films of the neat resin had a lower 50 wt.% loss temperature compared with that of the same resin in the formulation.

Synthesis, characterization, and hyperpolarizability measurements of main-chain azobenzene molecules - Smitha, P.; Asha, S. K.; Pillai, C. K. S. (Journal of Polymer Science Part A: Polymer Chemistry, 2005)
A series of new AB type azobenzene monomers based on various substituted phenols and higher order fused/extended aromatic rings were synthesized and their hyperpolarizability tensor β determined by hyper-Rayleigh scattering (HRS) measurement in methanol. The electron donor ([BOND]OH) and acceptor units ([BOND]COOH) were kept constant in the series, but the effective conjugation length was varied by varying the number and position of substituents as well as the number of aromatic rings. The effect of substitution of the phenolic ring on the β value was investigated and it was found to range from 15 × 10−30 to 42 × 10−30 esu. The effect of intramolecular hydrogen bonding on the nonlinear optical (NLO) property was also examined. The nonlinearity was in the following order of phenol derivative: α-naphthol > phenyl phenol > 2,6-dimethyl phenol > o-cresol > cardanol > phenol > β-naphthol. The unusually low values for the β-naphthol-based chromophore compared with its isomer (α-naphthol) could be rationalized based on hydrogen bonding of the o-hydroxyl group with the β nitrogen of the azo bridge. These azobenzene NLO chromophoric monomers were polymerized to form main-chain polymers with a head to tail structure. The polymers had high thermal stability and rather low solubility in common organic solvents. © 2005 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 43: 4455–4468, 2005

Control of molecular structure in the generation of highly luminescent liquid crystalline perylenebisimide derivatives: synthesis, liquid crystalline and photophysical properties - Jancy, B.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
We report here, for the first time, the role of the molecular design on the liquid crystalline and solid-state photoluminescent properties of soluble and thermally stable liquid crystalline perylenebisimide derivatives. A new series of perylenebisimides were designed and developed for this purpose by adopting the stoichiometry-control approach, and amine-, hydroxyl-, ester-, and amide-functionalized molecules were synthesized. Various types of spacers with different lengths (C2 to C12), types (linear, cyclohexyl, and tricyclodecane), and end-capped by phenyl or tridodecyloxy gallic units were introduced in the perylenebisimide core. The molecules were completely characterized by NMR, FT-IR, SEC, and MALDI-TOF mass techniques. Thermal analysis revealed that the perylenebisimide derivatives were thermotropic liquid crystalline, and threadlike nematic phases were observed under a polarizing light microscope. The spacer length and the rigidity of the spacers play a major role in the liquid crystalline properties of the materials. In phenyl systems, the C6 chain with ester- and the C12 chain with amide-end-capped molecules showed a nematic phase, whereas the C6 chain with an amide end cap and their cyclic and tricyclic counterparts did not show any LC property. The introduction of a tridodecyloxy gallic unit induced the LC property in C12 and the cyclohexyl system; however, it failed to do so in the tricyclodecane molecule. The absorption properties of the molecules were almost unchanged by the structural variation; however, the emission quantum yield in solution and photoluminescent (PL) intensity in the solid state were significantly different. Though the gallic unit induced liquid crystallinity in the perylenebisimide core, the quantum yield and PL intensity are 4−5 times less compared to those of the simple phenyl-capped liquid crystalline system. Among the various types of spacers, the tricyclodecane induced strong molecular aggregates via π-stacking, which in turn increased the rigidity of the entire perylenebisimide core, resulting in the absence of liquid crystallinity and low luminescence compared to their linear and cyclohexyl analogues. The molecular aggregates were very stable even at very dilute concentration and also at high temperatures. The aggregates disappeared immediately upon addition of trifluoroacetic acid, thus confirming the strong hydrogen bonding in the aggregated states. In a nutshell, the present report demonstrates the importance of molecular design for introducing liquid crystalline phases in perylenebisimides and also the development of novel highly luminescent n-type π-conjugated material for application in optoelectronics.

Hydrogen bonding and rate enhancement in the photoinduced polymerization of telechelic urethane methacrylates based on a cycloaliphatic system: tricyclodecane dimethanol - Deepak, V. D.; Rajan, J.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2006)
A new class of telechelic urethane methacrylic crosslinkers, based on a cycloaliphatic system (tricyclodecane dimethanol and tricyclodecane monomethanol), was synthesized. The synthesis was achieved by a two-step condensation of 1,6-hexamethylene diisocyanate or isophorone diisocyanate with tricyclodecane dimethanol and capping with hydroxyethyl methacrylate. Samples of hexanediol diacrylate, tricyclodecane monomethacrylate, and tricyclodecane dimethacrylate were used as non-hydrogen-bonding monomers for comparative studies of the curing kinetics. The photopolymerization of these telechelic systems was investigated with UV irradiation in the presence of 2,2-diethoxy acetophenone as the photoinitiator, and the kinetics were followed by the monitoring of the double-bond conversion at 815 cm−1 with Fourier transform infrared spectroscopy. The hydrogen-bonded crosslinkers had higher double-bond conversions than their non-hydrogen-bonded counterparts under identical conditions. The higher cure rate could be explained by hydrogen-bonding preassociation in these systems, which brought the methacrylate double bonds within close proximity. The temperature effects on the hydrogen bonding were also investigated. A decrease in the extent of the double-bond conversion with increasing temperature was observed for the hydrogen-bonded crosslinker, in contrast to an increased conversion with temperature for hexanediol diacrylate and tricyclodecane dimethacrylate. This was directly indicative of a reduction of hydrogen bonding at elevated temperatures leading to lower conversions. © 2006 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 44: 4384–4395, 2006

Self-organization-induced three-dimensional honeycomb pattern in structure-controlled bulky methacrylate polymers: - Deepak, V. D.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
Here we report, for the first time, a novel molecular design for three-dimensional honeycomb structures through a self-organization of hydrogen-bonded bulky anchoring group in a methacrylic polymer backbone. The polymerizable monomer design includes a methacrylic double bond linked to various hydrophobic anchoring units such as ethane, n-decane, tricyclodecane (TCD), and adamantane via a hydrogen-bonded cycloaliphatic urethane linkage. The structures of the polymers were confirmed by nuclear magnetic resonance (NMR) and the molecular weights of the polymer were determined by gel permeation chromatography (GPC). The methacrylate polymers having tricyclodecane and adamantane bulky anchoring groups self-organized to produce three-dimensional honeycomb patterns in tetrahydrofuran−water solvent mixture at ambient conditions, whereas its linear analogues (ethane, n-decane) failed to produce any micropattern. The scanning electron microscopy (SEM) analysis of the above-prepared polymer films revealed that the structure of the polymer played a major role in the formation of the honeycomb patterns. The solution Fourier transform infrared (FTIR) measurements confirmed that the bulky tricyclodecane and adamantane polymers have strong hydrogen-bonding interaction compared to that of their linear analogues, which is the driving force for the micropatterns. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) analysis of the bulky polymers revealed that the polymers exist as vesicles or micelles in the solution, which leads to the formation of the honeycomb pattern. The honeycomb pattern formation in the bulky polymer systems suggests that two cooperative factors such as hydrogen-bonding interaction and hydrophobicity of bulky anchoring units are necessary to induce three-dimensional honeycomb structures. To investigate the effect of molecular weights and its distribution on the self-organization process, both benzoyl peroxide (BPO) initiated free radical and atom transfer radical polymerization (ATRP) techniques were employed for the polymerization. Micropores formed irrespective of differences in molecular weight and polydispersity index (PDI); however, the pore size distribution was influenced by both molecular weights and PDI. Low molecular weight samples afforded polydisperse pores with the ATRP samples with more narrow PDI producing pores with large dimensions. The approach has also been investigated for polystyrene-bulky methacrylic copolymer, and the results revealed that uniform honeycomb patterns were produced for copolymers having more than 50 mol % incorporation of bulky units.

Structure control for fine tuning fluorescence emission from side-chain azobenzene polymers - Smitha, P.; Asha, S. K. (Journal of Physical Chemistry B, 2007)
New fluorescent azobenzene dyes and side-chain polymers have been synthesized and characterized and their photophysical properties studied. A series of azobenzene dyes having different fluorophores such as phenol (S1), phenylphenol (S2) and naphthol (S3) incorporated in them were synthesized. S2 had unusually high fluorescence with a quantum yield of φf = 0.2 recorded in dichloromethane (DCM), whereas S1 and S3 were found to be weakly fluorescent. The azobenzene dyes were converted into methacrylate monomers having short ethyleneoxy spacers and then free radically polymerized. Phenylphenol-based azobenzene polymer (P2) continued to show fluorescence, whereas fluorescence was completely quenched in the case of phenol (P1)- and naphthol (P3)-based polymers. Phenylphenol, though twisted in the ground state is known to have a more planar geometry in the excited statea factor that enables it to retain its fluorescence behavior even when it is incorporated as part of an azobenzene unit. In contrast, naphthol, which is a better fluorophore compared to phenylphenol, loses much of its emissive behavior upon coupling to the azobenzene unit. The extent of trans to cis photoisomerization in solution was very low (∼17%) for P2 after 30 min of continuous irradiation using 365 nm light, in contrast to ∼ 40% for P1 under identical conditions. This is attributed to the steric repulsion brought about by the bulky phenylphenol units that restrict rotation. A 2-fold enhancement in fluorescence emission was observed for P2 upon irradiation by UV light at 360 nm, which relaxed to the original intensity in about 7 day's time. The higher emission of the cis azobenzenes is generally attributed to an inhibition of photoinduced electron transfer (PET) mechanism. The emission of P2 showed a concentration dependence which increased initially and then decreased in intensity with the formation of a new red-shifted peak at higher concentration due to aggregation. Irradiation of the fluorescence quenched highly concentrated (1 × 10-3 M) sample of P2 showed an enhancement in emission from aggregates at 532 nm.

Hydrogen-bonding-induced conformational change from J to H aggregate in novel highly fluorescent liquid-crystalline perylenebisimides - Jancy, B.; Asha, S. K. (Chemistry of Materials, 2008)
A series of highly fluorescent liquid-crystalline perylenebisimide molecules having amide or ester linkage and end-capped by phenyl, monododecyloxy phenyl, or tridodecyloxy phenyl units have been synthesized and fully characterized. The amide-functionalized series self-organized to form H type aggregates regardless of their end-capping in organic solvents like tetrahydrofuran (THF), toluene, and dichloromethane. On the other hand, only the monododecyloxy phenyl end-capped molecule in the ester series showed a tendency to self-organize with a typical J type aggregation in toluene. In both series, the highest aggregation tendency was shown by the one having monododecyloxy phenyl end-capping, with the transition temperature from aggregated to molecularly dissolved species occurring at 60 °C for the amide and 50 °C for the ester molecule. At higher concentrations in toluene, the fluorescence spectra of the monododecyloxy phenyl and tridodecyloxy phenyl terminal-substituted amide derivatives showed the formation of a new peak corresponding to excimer emission at 670 nm. Thin drop cast films of the perylenebisimide ester and amide series gave only excimer emission ∼670 nm upon excitation. Thermal analysis using differential scanning calorimetry (DSC), polarized light microscopy (PLM), and powder X-ray diffraction measurements were utilized to study the liquid-crystalline (LC) characteristics of the molecules. Scanning electron micrograph (SEM) of thin drop-cast samples that were annealed in toluene showed the formation of supramolecular rods several micrometers in length, especially for the amide derivatives. The ester derivative, on the other hand, showed a leaflike morphology thus differentiating it from the amide series, which have both hydrogen bonding and π−π interactions to support self-organization.

Random and AB diblock copolymers of tricyclodecanemethanol urethane methacrylate with styrene: synthesis and morphology characterization - Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2008)
A monomer design having a bulky terminal tricyclodecane (TCD) unit linked via hydrogen bondable urethane to an ethyleneoxy methacrylate unit, and capable of generating three-dimensional honeycomb patterns upon solvent casting has been investigated. Random copolymers as well as a diblock copolymer Poly(Sty42-b-TCD18) of this monomer with styrene were prepared by free-radical polymerization route and atom transfer radical polymerization (ATRP) route. Morphology characterization was carried out using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis. Particle size was measured by dynamic light scattering measurements (DLS). Irrespective of the wide differences in molecular weight and polydispersity index values, the random copolymers having TCD content >30 mol % were found to form microporous films upon solvent casting from a THF/water 9:1 solvent combination. The amount of TCD in the copolymer was found to have an influence on the pore size formed. The diblock copolymer formed microspheres ∼200 nm in diameter. The thermal properties of all the polymers were studied using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), and the copolymers were found to have good thermal stability. © 2008 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 46: 1278–1288, 2008

Synthesis and FTIR spectroscopic investigation of the UV curing kinetics of telechelic urethane methacrylate crosslinkers based on the renewable resource-cardanol - Rekha, N.; Asha, S. K. (Journal of Applied Polymer Science, 2008)
UV curable telechelic urethane-methacrylate crosslinkers based on the natural resource-cardanol was synthesized in a one pot synthetic step involving end capping of isophorone diisocyanate with one equivalent of hydroxyethyl methacrylate followed by condensation with cardanol. The structures of the resins were characterized by H-1 and C-13 NMR, fourier transform infrared (FTIR) and Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) spectroscopies and size exclusion chromatography (SEC). The curing process and double bond conversion in presence of 2,2-diethoxy acetophenone as photo-initiator upon UV irradiation was followed by Fourier transform infrared spectroscopy. These hydrogen bonded crosslinkers based on cardanol and its derivatives had higher double bond conversion when compared to a nonhydrogen bonding standard such as hexanediol diacrylate (HDDA) under identical conditions. The temperature effects on the hydrogen bonding were investigated, and a decrease in the extent of double bond conversion with increase in temperature was observed for the telechelic urethane-methacrylate crosslinkers whereas a steady increase in the curing rate was observed for HDDA. This gives direct indication of the influence of hydrogen bonding on the curing process. (C) 2008 Wiley Periodicals, Inc.
Keywords: Cardanol; hydrogen bonding; infrared spectroscopy; renewable resource; UV curing

Photophysical investigation into the self-organization in pyrene-based urethane methacrylate comb polymer - Deepak, V. D.; Asha, S. K. (Journal of Physical Chemistry B, 2009)
A side chain urethane methacrylate polymer with pendant pyrene units was synthesized and investigated for its self-organizing process in solution by UV-vis and fluorescence spectra and in film by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and fluorescence microscopy. The polymer exhibited excimer emission centered at 476 nm, even at very dilute concentrations (10(-6) M) as a consequence of the polymer design with pendant pyrene units on every side chain. A change in aggregation pattern was observed upon increasing the concentration to 10(-4) M. New red-shifted peaks appeared in the UV-vis absorption spectra and the I(E)/I(M) ratio, and the peak I/peak III ratio showed a break around 10(-4) M, suggesting formation of stable ground state aggregates. This was further confirmed by the SEM, TEM, AFM and fluorescence microscope studies, which showed the formation of vesicles in THF and giant spherical aggregates in THF/H(2)O. The change in pattern of aggregate formation with concentration also coincided with a sudden increase in the intensity of the hydrogen bonded urethane N-H peak with concentration as recorded by solution FT-IR studies in THF.

Solvent-induced self-assembly in cardanol-based urethane methacrylate comb polymers - Rekha, N.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
We report side chain urethane-methacrylate comb polymers based on the renewable resource cardanol and its saturated analogue 3-pentadecyl phenol and their self-assembly into pores, spheres, vesicles, tubes, and so forth. The monomers were synthesized in one pot by coupling 1 equiv. of isophorone diisocyanate with 1 equiv. of cardanol/pentadecyl phenol followed by coupling with 1 equiv. of hydroxyethyl methacrylate. They were polymerized free radically using benzoyl peroxide as the initiator and were characterized by NMR and FTIR, and their molecular weights were determined by gel permeation chromatography. The unique polymer design had sites for self-organization via hydrogen bonding of the side chain urethane units, pi-pi stacking interactions of the aromatic units as well as interdigitation of the long C(15) alkyl side chains in the polymer. The morphologies of solvent cast polymer films were studied using microscopic techniques such as scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. The polymers exhibited three-dimensional honeycomb morphology in CHCl(3), whereas in tetrahydrofuran, they formed spheres. The direct cardanol-derived polymer PCIH showed a tendency for multiple morphologies such as spheres and tubes in tetrahydrofuran. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2996-3009, 2009
Keywords: Morphology; polyurethanes; Renewable resources; self-organization

Synthesis and self-organization properties of copolyurethanes based on perylenediimide and naphthalenediimide units - Jancy, B.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A series of perylene and naphthalene diimide-containing random copolyurethanes with different ratios of perylene/naphthalene diimide content was synthesized and characterized. Copolymerization improved the solubility of these rigid aromatic diimides, and the copolymers were soluble in common organic solvents like chloroform, tetrahydrofuran, and so forth. The absorption spectra of perylene-based copolymers showed a red-shifted peak at a wavelength of 557 nm corresponding to J-type aggregates. For naphthalene copolymers, the quenching of fluorescence at higher naphthalene incorporation suggested the presence of aggregates because of the extensive pi-pi stacking of the aromatic core. FTIR spectroscopic analysis showed that the hydrogen bonding tendency of the polymer decreased with increase in perylene/naphthalene incorporation. The fluorescence spectra of the perylene polymers were exactly a mirror image of the absorption spectra. The fluorescence spectra of the naphthalene polymers at higher naphthalene incorporation showed a red-shifted excimer like emission peak, which was assigned as static excimers based on their excitation spectra. These polymers could exhibit two types of secondary interaction modes, namely, hydrogen bonding (via urethane linkage) and pi-stacking (via aromatic perylene or naphthalene units) thus highlighting the importance of polymer design in inducing self-organization at both low and high incorporation of the rigid bisimide moieties. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polyrn Chem 47: 1224-1235, 2009
Keywords: fluorescence; hydrogen bonding; naphthalene diimide polymers; polyurethane copolymer; self-organization; structure-property relations

N-Type field effect transistors based on rigid rod and liquid crystalline alternating copoly(benzobisoxazole) imides containing perylene and/or naphthalene - Kolhe, Nagesh B.; Asha, S. K.; Senanayak, Satyaprasad P.; Narayan, K. S. (Journal of Physical Chemistry B, 2010)
The synthesis, characterization, and device studies of poly(benzobisoxazole imide)s containing perylene or naphthalene units in an alternating fashion with the oxazole unit are described. Photoinduced energy transfer and charge separation were studied in methanesulfonic acid (MSA) solution via absorption, excitation, and steady-state fluorescence studies. Excitation of the bisoxazole moiety resulted in enhanced emission from the perylene bisimide unit as a result of FRET (Forster resonance energy transfer). The influence of the imide substitution into the linear chain of poly(benzobisoxazole) (PBO) on its solid-state packing was examined by wide-angle X-ray diffraction (WXRD) analysis. Bottom contact field effect transistors (FET) based on thermally annealed polymer films were fabricated and studied. The polymers showed n-type charge transport and current modulation with an on/off ratio greater than 10(2). It was observed that the FETs consisting of the random copolymer of bisoxazole containing both perylene as well as naphthalene bisimide units had higher performance parameters such as better mobility (mu e) and I(on)/I(off) ratio compared to those of the pristine systems.

Correlation of architecture with excimer emission in 100% pyrene-labeled self-assembled polymers - Kaushlendra, K.; Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2011)
Pyrene was incorporated as pendant unit to side-chain urethane methacrylate polymers having a short ethyleneoxy or a long polyethyleneoxy spacer segment. The short-spacer pyrene urethane methacrylate was also incorporated either as block or random copolymer (1:9) along with polystyrene. The excimer emission was observed to be different for different polymers with the random copolymer exhibiting the lowest efficiency. But, the total quantum yield was highest (phi = 0.58) for random copolymer due to the high emission coefficient of monomer compared to that of excimer. The polymer dynamics were compared by steady state emission and fluorescence decay in THF or THF/water (9:1) solvent mixture and films. The solid state decay profile showed decay without a rise time indicating presence of ground state aggregates. In THF/water (9:1), the decay profile at the excimer emission (500 nm) showed a rise time indicating dynamic excimers. The evolution of excimeric emission centred similar to 430 or similar to 480 nm as a function of temperature was also studied in THF/water (9:1). The I(E)/I(M) ratio for the lambda(343) nm excitation exhibited steady increase with temperature with the block copolymer PS-b-PIHP exhibiting the highest ratio and highest rate of increase; whereas, the random copolymer PS-r-PIHP had the lowest I(E)/I(M) ratios. (C) 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 49: 1678-1690, 2011
Keywords: I(E)/I(M) ratio; Morphology; pyrene; Self-assembly; structure-property relations; time-resolved and variable temperature fluorescence

Pentadecyl phenol- and cardanol-functionalized fluorescent, room- temperature liquid-crystalline perylene bisimides: effect of pendant chain unsaturation on self-assembly - Bhavsar, Ghanashyam A.; Asha, S. K. (Chemistry - A European Journal, 2011)
A new perylene bisimide (PBI) building block based on pentadecyl phenol (PDP) or cardanol was developed, which upon esterification with 3,4,5-tridodecyloxy gallate resulted in highly emissive, room-temperature liquid-crystalline (LC) molecules. The self assembly in solution was studied in detail by NMR spectroscopy, UV/Vis absorption, and fluorescence spectroscopy. In solution both PDP- and cardanol-based PBI exhibited similar behavior. They were molecularly dissolved in chloroform (CHCl3) but formed rotationally displaced H-type aggregates that emitted at 640 nm in methylcyclohexane (MCH). Surface morphology in dropcast films were characterized using microscopic techniques such as SEM, TEM, and atomic force microscopy (AFM). The liquid-crystalline properties were studied using differential scanning calorimetry (DSC), polarized light microscopy (PLM), and variable-temperature X-ray (small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WXRD)) studies. Variable-temperature X-ray studies in the LC phase indicated strong π–π stacking interaction present in the PDP-based PBI derivative, whereas the stacking was absent in the LC phase of the cardanol-based PBI. The latter formed self-organized structures of extremely short length due to the presence of cis double bonds in the C15 alkyl side chain, whereas the saturated alkyl side chain in PDP could pack efficiently, thereby resulting in nanofibers that were several micrometers in length.

Microstructural reorganization and cargo release in pyrene urethane methacrylate random copolymer hollow capsules - Kaushlendra, K.; Asha, S. K. (Langmuir, 2012)
We report the synthesis of polymer microcapsules by direct one-pot free radical random copolymerization approach. Urethane methacrylate comb monomers having pendant pyrene (Py) and 3-pentadecyl phenol (PDP) units were copolymerized in a random manner using benzoyl peroxide (BPO) as free radical initiator in dimethylformamide (DMF) as solvent. These copolymers and corresponding homopolymers spontaneously self-organized into microspheres upon drop casting from solvents like DMF and tetrahydrofuran (THF). Stable microspheres were obtained in water by dialyzing THF solution of the polymers against water in dialysis bags with molecular weight cutoff of similar to 2000. The hollow nature of the spheres was confirmed by rhodamine B (RhB) encapsulation followed by Forster resonance energy transfer (FRET) based fluorescence emission from RhB upon exciting pyrene. The microenvironment inside the capsule was probed by following the I-1/I-3 ratio of pyrene emission as well as RhB release as a function of temperature. The RhB encapsulated in the pyrene homopolymer PIHP-100Py capsules experienced strong donor-acceptor interaction and did not undergo complete release even at high temperature (85 degrees C). The encapsulated RhB from the copolymers with low pyrene incorporation was released almost fully upon heating beyond 50 degrees C. Pyrene moieties in the PIHP-100Py were shielded from surrounding water and experienced a hydrophobic environment, whereas in the low pyrene incorporated copolymer the PDP units were better shielded from the hydrophilic environment. This work represents a simple approach to produce polymer hollow capsules, and the varying pyrene incorporation was used to trace the microenvironment inside the capsules.

Structure engineering of naphthalene diimides for improved charge carrier mobility: self-assembly by hydrogen bonding, good or bad? - Kolhe, Nagesh B.; Devi, R. Nandini; Senanayak, Satyaprasad P.; Jancy, B.; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry, 2012)
Two families of naphthalene diimide (NDI) derivatives were compared and contrasted for the effect of self-assembly on charge carrier transport. One series of NDI derivatives had a terminal phenyl ring attached to a hexyl spacer substituted naphthalene core either through an ester or an amide linkage (NDI-E and NDI-A, respectively), while the other series had a 3,4,5-tridodecyloxy phenyl unit (NDI-E3, NDI-A3) instead of the terminal phenyl unit. Solution processed thin films of these molecules exhibited n-type charge transport characteristics in a bottom gate top contact organic field effect transistor (OFET) geometry. The amide derivatives showed evidence of self-organization with observation of red shifted aggregate emission in solution as well as solid state. Variable temperature FTIR studies in the solid state confirmed the existence of strong hydrogen bonding which could be broken only at very high temperature. However, contrary to expectations, the NDI ester derivatives showed better device efficiency with electron mobilities in the range 8.5 x 10(-3) to 2 x 10(-2) cm(2) V-1 s(-1) and on/off ratio similar to 10(4). The thin film crystallinity and morphology of NDI-E and NDI-A were examined through X-ray diffraction and atomic force microscopy (AFM). The correlation of crystallinity, hydrogen bonding and charge carrier mobility was studied using energy minimized structures from density functional theory (DFT). The higher electron mobility of ester linked NDI derivatives over the amide linked ones was attributed to the freedom in charge transport pathways offered by a three dimensional crystalline organization in the ester compared to the restricted directional hydrogen bonding interaction in the amide derivatives.

Twin liquid crystals and segmented thermotropic polyesters containing azobenzene?effect of spacer length on LC properties - Nardele, Chinmay G.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2012)
We report systematic studies on a homologous series of twin liquid crystalline (LC) molecules based on phenyl and naphthyl azobenzene (PnP and NpnNp) as well as segmented copolyesters based on them. The twin series had the structure azobenzene–oligooxyethylene–azobenzene, where the ethyleneoxy length was varied from 2 to 6 units. The LC properties of the twin series depended on the chemical structure of the azochromophore and also the length of the central oligooxyethylene segment. The PnP series exhibited smectic LC properties for n > three oligooxyethylene units. Conversely, NpnNp series exhibited spherulitic phases only for the shortest member –Np2Np. One non-LC short spacer twin (P2P) and one LC long spacer twin (P6P) were incorporated as part of a main chain polyester composed of fully aliphatic segments of sebacate and di or tetraethylene glycol (DEG/TEG) units by melt polycondensation. Non-LC P2P formed LC polymers even at low (5 mol %) incorporation in DEG-based copolymers, whereas the LC-P6P could do so only at 30 mol % incorporation. The LC properties of the twin molecules as well as copolymers were studied using differential scanning calorimetry, polarized light microscopy (PLM) along with variable temperature wide angle X-ray diffraction. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2012

Charge storage and electron transport properties of gold nanoparticles decorating a urethane-methacrylate comb polymer network - Patil, Sumati; Datar, Suwarna; Rekha, N.; Asha, S. K.; Dharmadhikari, C. V. (Nanoscale, 2013)
We propose enhanced charge storage capacity of nanoparticles based polymer films. A flat band voltage window varying from 5-7 V is obtained leading to a trapped charge density of the order of 10(13) cm(-2). These results vary for two distinct morphologies obtained due to decoration of a urethane-methacrylate comb polymer (UMCP) network by gold nanoparticles (AuNPs). Films have been further investigated for morphology, optical, charge storage, and electron transport properties using techniques like scanning electron microscopy (SEM), atomic force microscopy (AFM), absorption spectroscopy (UV-Vis), scanning tunneling microscopy/spectroscopy (STM/STS) and capacitance versus voltage (C-V) measurements. SEM and AFM confirm either the deposition of AuNPs inside the UMCP network or the formation of ring like structures depending on the deposition sequence. STS measurements performed on both films are compared with bare UMCP and AuNPs films. Current versus voltage (I-V) characteristics so obtained are discussed in the light of electron transport mechanisms in such materials.

Donor-acceptor random copolyesters containing perylenebisimide (PBI) and oligo(p-phenylene vinylene) (OPV) by melt condensation polymerization: energy transfer studies - Nisha, S. Kumari; Asha, S. K. (Journal of Physical Chemistry B, 2013)
Novel copolyesters consisting of oligo(p-phenylene vinylene) (OPV) as donor (D) and perylenebisimide (PBI) as acceptor (A) were synthesized by melt polycondensation. Photoinduced energy transfer and photoinduced charge separation in these polyesters were studied in solution as well as in the solid state. Selective excitation of OPV moiety resulted in the energy transfer with >90% efficiency from OPV to PBI chromophore in the solution state. The direct excitation of PBI in the D A copolyester resulted in reduced fluorescence emission of acceptor, indicating electron transfer between the D and A moieties. The effect of distance between donor and acceptor on the energy transfer efficiency from donor to acceptor was studied. Compared to a physical mixture of D and A polyesters alone, the energy transfer was 4 times more efficient in the D A copolyester, highlighting the influence of covalently linking D and A in a single polymer chain. A strong fluorescence quenching (similar to 100%) of both chromophores in solid state indicated an efficient photoinduced charge transfer after photoexcitation of either D or A. Thus, OPV-PBI main chain copolyester is an excellent system for the study of energy- and electron-transfer processes in organic semiconductor. Reactive blend of D/A copolyester was also prepared by the transesterification reaction between D and A alone copolyesters. The energy transfer efficiency from D to A moiety upon selective excitation of D chromophore in the D/A copolyester blend was similar to 4 times higher compared to a physical mixture of D and A alone copolyesters, which gave direct proof for the transesterification reaction in polyester/polyester reactive blending.

Facile one-pot reactive solution blending approach for main-chain donor-acceptor polymeric materials - Nisha, S. Kumari; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
A high-temperature solution blending process has been used to synthesize a series of copolymers incorporating varying mole ratios of perylenebisimide (PBI) into the backbone of an engineering thermoplastic polyester [poly(1,4-cyclohexylenedimethylene-1,4-cyclohexanedicarboxylate)] (PCCD). A random donor-acceptor copolymer incorporating oligo(p-phenylene vinylene) (OPV) and PBI was also synthesized. The chemical incorporation of these chromophores into PCCD was confirmed by carrying out the melt condensation using 1,4-cyclohexanedimethanol and 1,4-dimethylcyclohexane dicarboxylate with hydroxyl-functionalized PBI and OPV derivatives. Higher extent of incorporation of PBI (35 mol %) could be achieved using the blending approach retaining solubility, film-forming ability, and higher molecular weights. The PBI polymers produced using the two different approaches exhibited structural variations. The polymers formed from the solution blending approach had a semicrystalline nature with blocks of PCCD separating the PBI units, whereas those produced using the melt condensation route were amorphous polymers. This structural variation was reflected in their photophysical properties also with the reactive solution-blended polymers exhibiting higher fluorescence quantum yields. These results demonstrate the easy incorporation of suitably functionalized donor and acceptor moieties into a completely aliphatic polyester backbone to produce free-standing films of hitherto nonprocessable polymers. (C) 2012 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 509-524
Keywords: blending; conjugated polymers; fluorescence; PCCD; Perylenebisimide; reactive blending; transesterification

Fluorescent cross-linked polystyrene perylenebisimide/oligo(p-phenylenevinylene) microbeads with controlled particle size, tunable colors, and high solid state emission - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2013)
A series fo cross-linked fluorescent polystyrene (PS) microbeads with narrow size distribution and intense solid state emission was developed. Fluorophores based on perylene bisimide (PBI) and oligo(p-phenylenevinylene) (OPV) designed as acrylic cross-linkers were introduced into the polymerization recipe in a twostage dispersion polymerization, carried out in ethanol in the presence of poly(vinylpyrrolidone) (PVP) as stabilizer. The structural design permitted introduction of up to 10(-5) moles of the fluorophores into the polymerization medium without fouling of the dispersion. The particle size measured using dynamic light scattering (DLS) indicated that they were nearly monodisperse with size in the range 2-3 mu m depending on the amount of fluorophore incorporated. Fluorescence microscope images of ethanol dispersion of the sample exhibited intense orange red emission for PS-PBI-X series and green emission for PS-OPV-X series. A PS incorporated with both OPVX and PBIX exhibited dual emission upon exciting at the OPV wavelength of 350 nm and PBI wavelength of 490 nm, respectively. The low incorporation of fluorophore resulted in almost complete absence of aggregation induced reduction in fluorescence as well as red-shifted aggregate emission. The solid state emission quantum yield measured using integrating-sphere setup indicated a very high quantum yield of phi(powder) = 0.71 for PSOPV-X and phi(powder) = 0.25 for PS-PBI-X series. The cross-linked PS microbeads incorporating both OPV and PBI chromophores had a phi(powder) = 0.33 for PBI emission and phi(powder) = 0.20 for OPV emission. This strategy of introducing fluorophore as crosslinkers into the PS backbone is very versatile and amenable to simultaneous addition of different suitably designed fluorophores emitting at different wavelengths.
Keywords: dispersion polymerization; dual emission; fluorescent cross-linker; oligo(p-phenylenevinylene); Perylenebisimide; solid state fluorescence

Nanostructured crystalline comb polymer of perylenebisimide by directed self-assembly: poly(4-vinylpyridine)-pentadecylphenol perylenebisimide - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Advanced Functional Materials, 2013)
Well defined nanostructured polymeric supramolecular assemblies are formed when an asymmetric perylenebisimide substituted with ethylhexyl chains on one end and functionalized with 3-pentadecylphenol at the other termini (PDP-UPBI) is complexed with poly(4-vinylpyridine) (P4VP) via a non-covalent specific interaction such as hydrogen-bonding. The resulting P4VP(PDP-UPBI)(n) complexes are fully solution processable. The bulk structure and morphologies of the supramolecular film studied using small angle and wide angle X-ray scattering reveals highly crystalline nature of the complex. Thin film morphology of the 1:1 complex analyzed using transmission electron microscopy shows uniform lamellar structures in the domain range of 5-10 nm. A clear trend of improved electrical parameters in P4VP(PDP-UPBI) system compared to pristine (PDP-UPBI) is observed from space charge limited current measurements. In short, a simple and facile method to obtain spatially defined organization of n-type semiconductor perylenebisimide molecules using hydrogen bonding interactions with P4VP as the structural motif is showcased herein.

Self-assembly in tailor-made polyfluorenes: synergistic effect of porous spherical morphology and fret for visual sensing of bilirubin - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2013)
Two new fluorene-based homo- (PDP-PF) and copolymers (PDPPF-co-Ph) were synthesized with a bulky 3-pentadecylphenoxy (PDP) group appended hexyl chains at the 9, 9' position using Suzuki coupling polymerization. Investigation on the morphology of the polymers using microscopic techniques like TEM and AFM indicated formation of self-assembled nanostructures like vesicles by PDP-PF and porous spheres by PDPPF-co-Ph respectively. Dynamic as well as static light scattering studies (DLS, SLS) in THF also indicated the existence of self-assembled nanosized particles in solution with a shape factor (rho) of 0.76 and 0.96 for PDP-PF and PDPPF-co-Ph, respectively, confirming the existence of vesicles in the case of the former and spherical particles in the case of the latter polymer. The favorable photophysical properties of the polyfluorenes were taken advantage of for the selective sensing of unbound bilirubin (BR) in THF. A high energy transfer efficiency of 86% upon addition of bilirubin with color change from blue (polyfluorene emission) to green (FRET-induced bilirubin emission) was observed with PDPPF-co-Ph. Steady state fluorescence measurements gave a minimum donor-acceptor distance of 36 A(0) and time-resolved fluorescence decay measurements showed a reduction in average lifetime of PDPPF-co-Ph (from 450 to 240 ps) upon addition of bilirubin indicating efficient energy transfer. The open porous spherical assembly of PDPPF-co-Ph enabled better adsorption of the analyte, which along with the good spectral overlap resulted in greater efficiency for FRET-induced energy transfer. Sensing of unbound bilirubin was also attempted in THF/water solvent mixture in an effort to simulate the unbound (THF soluble) and bound (water-soluble) bilirubin equilibrium. Enhancement of bilirubin emission coupled with quenching of polyfluorene emission makes this approach adaptable for visual fluorimetric color change (blue to green) based sensor. Structural analogues such as biliverdin and porphyrin showed poor fluorescence quenching efficiency, thus highlighting the selectivity and sensitivity of the FRET-based sensing of bilirubin by the newly designed polyfluorene.

Solvent-induced self-assembly of hydrogen bonded P4VP-perylenebisimide comb polymer - Narayan, Rekha; Asha, S. K. (Journal of Materials Chemistry C, 2013)
Polymeric supramolecular assemblies were formed when an unsymmetric perylenebisimide substituted with ethylhexyl chains on one end and functionalized with 3-pentadecylphenol at the other termini (PDP-UPBI) was complexed with poly(4-vinylpyridine) (P4VP) via hydrogen-bonding interaction. The self-assembly behavior of this polymeric supramolecule poly(4-vinylpyridine)-perylenebisimide P4VP(PDP-UPBI)(1.0) was studied in solvents of varying polarity like chloroform (CHCl3) and methylcyclohexane (MCH). Variable concentration and variable temperature proton NMR studies in CDCl3 and deuterated 1,1,2,2-tetrachloroethane (TCE), respectively, revealed the polymeric nature of the perylenebisimide upon complexation and the high thermal stability of the self organized structures in solution. The improved solubility afforded by the complexation enabled variable temperature UV-Vis absorption studies in the non-polar solvent MCH, which indicated the existence of strong face-to-face stacked H-type aggregates. The strong fluorescence quenching in MCH also supported the identification of the nature of aggregates as co-facial H-type. Although the existence of aggregates was not very evident in dilute solutions of chloroform, the fluorescence of the P4VP(PDP-UPBI) 1.0 was quenched compared to that of PDP-UPBI. Thin spin coated films of the complex from chloroform exhibited features of rotationally displaced H-type aggregates characterized by blue shift of absorption maxima and the appearance of a new red shifted peak at 540 nm with weak aggregate emission beyond 600 nm. Morphology analysis of drop cast samples using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed the formation of micrometer long multilamellar nanofibers from CHCl3 and two dimensional multilamellar nanosheets upon switching the solvent to MCH.

Variable-temperature time-resolved emission spectra studies of random pyrene urethane methacrylate copolymers with high pyrene incorporation - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2013)
A series of random co-polyurethane methacrylate comb polymers with pyrene (Py) and 3-pentadecylphenol (PDP) as pendant units Were prepared by free radical polymerization. The pyrene labeling was varied from 1 to 100 mol %. The excimer emission of these copolymers were studied as a function of both time and temperature using time-resolved emission spectra (TRES) experiments and variable-temperature steady-state fluorescence measurements. Variable-temperature steady-state as well as decay experiments showed that the contribution from excimers via diffusional encounters increased at the cost of pyrene monomer as the temperature increased until similar to 50 degrees C; beyond which nonradiative losses predominated. TRES collected at 25 and 70 degrees C were compared to study the nature and origin of emitting species as a function of pyrene loading. TRES at 25 degrees C dearly indicated the presence of ground state pyrene dimers with emission centered at similar to 435 nm which soon gave way to emission centered around 465 and 485 nm in the time gated spectra collected at higher time intervals. In TRES collected at 70 degrees C, excimer emission centered at 465 and 485 nm was very high even at short time scales. The lowest pyrene loaded polymer PIHPDP-1Py did not exhibit excimer emission in the TRES collected at 25 degrees C as well as 70 degrees C.

Blue, green, and orange-red emission from Polystyrene microbeads for solid-state white-light and multicolor emission - Sonawane, Swapnil L.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
Solid-state white-light emission was achieved from polystyrene (PS) microbeads incorporated with fluorophores based on perylene bisimide (PBITEG) and oligo(p-phenylenevinylene) (OPV) as acrylic cross-linkers. The PS beads incorporated with only PBITEG gave intense orange-red emission; PS incorporated with OPV exhibited blue-emission, whereas a series of polymers incorporating both cross-linkers exhibited varying shades of white-light emission. One of the PS samples, PS-PBITEG-6.25-OPV-4.28 (PBITEG incorporation: 6.25 X 10(-7) mole; OPV incorporation: 4.28 x 10(-7) mol), exhibited pure white-light emission in the powder form with CIE coordinates (0.33, 0.32). The rigid aromatic cross-linkers were incorporated into the PS backbone in a two-stage dispersion polymerization to afford PS beads in the size range 2 to 3 mu m. The incorporation of fluorophores as cross-linkers enabled covalent attachment of the dye to the polymer backbone, avoiding dye leakage besides avoiding aggregation-induced fluorescence quenching.

Chiral poly(L-lactic acid) driven helical self-assembly of oligo(p-phenylenevinylene) - Nisha, S. Kumari; Asha, S. K. (Journal of Materials Chemistry C, 2014)
The synthesis and self-assembly of a series of copolyesters incorporating varying mol ratios of an achiral oligo(p-phenylenevinylene) (OPV) into the backbone of a chiral poly(L-lactic acid) (PLLA) via high temperature solution blending is reported. The polymers were characterized by H-1 NMR spectroscopy and size exclusion chromatography (SEC) and their bulk properties were investigated by differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WXRD). The DSC and WXRD analyses confirmed the crystallinity and pi-pi stacking of the OPV units in the PLLA-OPV copolyester. Absorption, emission and lifetime-decay studies showed that the OPV chromophore was highly aggregated in the solid state. The solid powder samples of the copolyesters exhibited an intense, red shifted aggregate emission beyond 470 nm. Circular dichroism (CD) spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM) studies revealed that the PLLA-OPV copolyester formed a self-assembled architecture, in which the helical organization of the achiral OPV segments was dictated by the chiral PLLA segments. The observed CD signal and AFM image accounted for the right-handed helical self-assembly of the OPV chromophore in the solid state. These results confirmed the effect of the chiral PLLA segment on tuning the OPV chromophore packing and supramolecular chirality in molecular aggregates. The methodology illustrated here provides opportunities for the design of a new class of hierarchical, self-assembled architectures, based on organic pi-conjugated materials and the manipulation of their optical properties.

H-bonding vs non-h bonding in 100% pyrene methacrylate comb polymers:self assembly probed by tres and temperature dependent fluorescence - Kaushlendra, K.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
The differences in self-organization behavior in novel 100% pyrene labeled comb methacrylate polymers probed as a function of their varied origins of excimer formation are presented. The different structural variations in the polymers included the presence or absence of hydrogen bonding interactions in the form of urethane linkages, short or long alkyl spacer segments separating the pyrene units from the polymer backbone and linear versus kinked urethane linkage. The effect of variable concentration and temperature on the chemical shift of the NH proton of the urethane linkage was probed using 1H NMR experiments conducted at temperatures varying from 25 to 70 °C at two different concentrations (2.5 and 25 mmol) in DMSO-d6 as solvent. The photophysical properties of the polymers in dilute DMF solutions were investigated by steady state emission, fluorescence decay studies, time-resolved emission spectra (TRES), and variable temperature emission studies. It was observed that the polymer poly(PBH) having a non-hydrogen-bondable ester linkage in the pendant chains formed an excimer completely via a static mechanism and the ground state aggregate species were not broken even at higher temperatures. The polymer poly(PIC) having a short hydrogen-bondable urethane linkage formed an excimer via a static as well as dynamic mechanism. The other hydrogen-bondable urethane methacrylate polymers having a linear linker poly(PHH) and kinked linker (PIHP) formed excimer mostly via a dynamic mechanism with a very small contribution from the static route. The TRES studies carried out for the polymers provided significant insight into the excimer formation mechanism in these polymers. The variable temperature fluorescence studies highlighted the differences in the H-bonded vs non-H-bonded polymer as a function of their excimer recovery upon cooling.

Nanostructured donor-acceptor self assembly with improved photoconductivity - Saibal, B.; Ashar, A. Z.; Devi, R. Nandini; Narayan, K. S.; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Nanostructured supramolecular donor-acceptor assemblies were formed when an unsymmetrical N-substituted pyridine functionalized perylenebisimide (UPBI-Py) was complexed with oligo(p-phenylenevinylene) (OPVM-OH) complementarily functionalized with hydroxyl unit and polymerizable methacrylamide unit at the two termini. The resulting supramolecular complex [UPBI-Py (OPVM-OH)](1.0) upon polymerization by irradiation in the presence of photoinitiator formed well-defined supramolecular polymeric nanostructures. Self-assembly studies using fluorescence emission from thin film samples showed that subtle structural changes occurred on the OPV donor moiety following polymerization. The 1:1 supramolecular complex showed red-shifted aggregate emission from both OPV (similar to 500 nm) and PBI (similar to 640 nm) units, whereas the OPV aggregate emission was replaced by intense monomeric emission (similar to 430 nrn) upon polymerizing the methacrylamide units on the OPVM-OH. The bulk structure was studied using wide-angle X-ray diffraction (WXRD). Complex formation resulted in distinct changes in the cell parameters of OPVM-OH. In contrast, a physical mixture of 1 mol each of OPVM-OH and UPBI-Py prepared by mixing the powdered solid samples together showed only a combination of reflections from both parent molecules. Thin film morphology of the 1:1 molecular complex as well as the supramolecular polymer complex showed uniform lamellar structures in the domain range <10 rim. The donor-acceptor supramolecular complex [UPBI-Py (OPVM-OH)](1.0) exhibited space charge limited current (SCLC) with a bulk mobility estimate of an order of magnitude higher accompanied by a higher photoconductivity yield compared to the pristine UPBI-Py. This is a very versatile method to obtain spatially defined organization of n and p-type semiconductor materials based on suitably functionalized donor and acceptor molecules resulting in improved photocurrent response using self-assembly.
Keywords: donor-acceptor; hydrogen bonding; oligo(p-phenylenevinylene); Perylenebisimide; photoconductivity; supramolecular polymeric nanostructures

Naphthalene diimide copolymers with oligo(p-phenylenevinylene) and benzobisoxazole for balanced ambipolar charge transport - Kolhe, Nagesh B.; Ashar, A. Z.; Narayan, K. S.; Asha, S. K. (Macromolecules, 2014)
A series of alternating and random donor (D)–acceptor (A) copolymers based on naphthalene diimide (NDI) as the acceptor and oligo(p-phenylenevinylene) (OPV) or benzobisoxazole (BBO) as the strong and weak donor, respectively, were designed and synthesized by Suzuki coupling and Horner–Wadsworth–Emmons polymerization. The effect of the varying donor strength of OPV and BBO on the photophysical, electrochemical, and semiconducting properties of the polymers was investigated. Absorption and emission spectra recorded for dilute chloroform solution and thin film showed increased intramolecular charge transfer for NDI-alt-OPV polymer compared to NDI-alt-BBO polymer. Cyclic voltammetry studies along with DFT (density functional theory) studies at the B3LYP/6-31g* level gave insight into the energy level (HOMO/LUMO) and molecular orientation of donor and acceptor along the polymer backbone. NDI-alt-OPV polymer exhibited rigid coplanar structure with extended π-conjugation which induced backbone planarity and crystallinity to the polymer. The inherent poor solubility of the NDI-alt-BBO prevented further device characterization of this polymer. Random copolymer having maximum 30% incorporation of BBO comonomer in NDI-r-OPV/BBO was found to be soluble for further characterization. Compared to NDI-alt-OPV, lowering of both energy levels LUMO (∼0.2 eV) and HOMO (∼0.5 eV) was observed for both NDI-alt-BBO and the NDI-r-OPV/BBO. Bottom gate–top contact organic field effect transistors (OFETs) of NDI-alt-OPV exhibited balanced ambipolar charge transport with average electron and hole mobility of 3.09 × 10–3 cm2 V–1 s–1 and 2.1 × 10–3 cm2 V–1 s–1, respectively, whereas the random copolymer incorporating both OPV and BBO units NDI-r-OPV/BBO showed dominant n-type charge transport with moderate 4 × 10–4 cm2 V–1 s–1 average electron mobility. The present work thus highlights the structure–property relationship and the electronic tunability required in this class of NDI-based polymers to produce ambipolar transistors.

Photoresponsive smectic liquid crystalline multipods and hyperbranched azo polymers - Nardele, Chinmay G.; Asha, S. K. (Journal of Physical Chemistry B, 2014)
Liquid crystalline azobenzene containing triped and tetraped monomers were designed and synthesized and further used as B-3 and B-4 type monomers to form hyperbranched polymers with tetraethylene glycol as the A(2) type comonomer. The mesophase characteristics of the multiarm-star mesogens and hyperbranched polymers were analyzed using various instrumentation techniques like differential scanning calorimetry (DSC), polarized light microscopy (PLM) and variable temperature XRD. The multipod monomers as well as hyperbranched polymers exhibited thermotropic smectic liquid crystalline characteristics with a tendency toward higher ordered smectic LC phases with increased branching. The hyperbranched polymers exhibited lamellar organization even in the as-solvent precipitated powder sample indicating higher extent of nanosegregation. Their potential application as fast switching photochromic materials was highlighted by carrying out isothermal photo-switching experiments in the LC state. Reversible isothermal smectic-isotropic phase transition could be achieved by UV irradiation in <1 s in the multipod monomers, while it required >2 s UV irradiation in the case of the hyperbranched polymers.

Random copolyesters containing perylene bisimide: flexible films and fluorescent fibers - Nisha, S. Kumari; Asha, S. K. (ACS Applied Materials & Interfaces, 2014)
Random copolyesters of poly(L-lactic acid) (PLLA) and [poly-(1,4-cyclohexylenedimethylene-1,4- cyclohexanedicarboxylate)] (PCCD) incorporating varying mol ratios of perylene bisimide (PBI) were developed via a high-temperature solution-blending approach. PCCD incorporating PBI was developed by melt polycondenzation followed by a polyester-polyester transesterification reaction between PCCD PBI and PLLA. The polymers exhibited good solubility in common organic solvents and formed free-standing films, which showed bright red emission upon irradiation with ultraviolet radiation. A solid state fluorescence quantum yield of 10% was observed for this PBI based polyester, which was much higher than that reported in literature for PBI based polymers in the solid state (<1%). Strong red fluorescent nanofibers of these polymers were successfully constructed by electrospinning technique. A random copolyester incorporating donor based on oligo(p-pheneylenevinylene) (OPV) and PBI as acceptor chromophore was also synthesized and fluorescence microscopy images of the electrospun fibers of this polymer exhibited blue, green and red emission upon excitation at different wavelengths. The high temperature solution blending approach involving a high molecular weight polymer and a suitably functionalized it conjugated molecule described here is a unique method by which 1D nanostructures of a wide range of pi-conjugated chromophores could be fabricated having strong fluorescence, with the scope of application in nanoscale optoelectronics, biological devices, as well as sensing.
Keywords: flexible film; fluorescent nanofibers; luminescent film; oligo(p-phenylenevinylene); perylene bisimide

Structure-property relationship in charge transporting behaviour of room temperature liquid crystalline perylenebisimides - Prajitha, K. P.; Chithiravel, Sundaresan; Krishnamoorthy, K.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A homologous series of pentadecyl phenol functionalized perylenebisimide (PBI) terminated with trialkoxy gallate esters was synthesized, where the terminal alkyl chain length was varied from n = 4 to 12 (PBI-En). The thermotropic liquid crystalline (LC) characteristics of the molecules were analyzed using differential scanning calorimetry (DSC), polarized light microscopy (PLM) combined with variable temperature wide angle X-ray diffraction (WXRD) techniques. A clear odd-even oscillation was observed in the melting as well as isotropization enthalpies as a function of alkyl spacer length in the terminal gallate unit, with the even spacers exhibiting higher values. The higher members of the series with n > 8 exhibited thermotropic liquid crystalline textures in the PLM, which remained stable until room temperature. The nature of the LC phase was identified to be columnar rectangular and columnar hexagonal based on detailed analysis of the WXRD pattern recorded in the LC phase. The WXRD pattern of the room temperature LC frozen samples indicated a nearly constant intra columnar stack distance of similar to 3.7 angstrom for all the members. The space-charge-limited current (SCLC) values of the LC frozen sample films were analyzed for dependence of the bulk mobility estimate on the nature of the LC phase. The columnar hexagonal phase exhibited a mobility value one order (10(-3) cm(2) V-1 s(-1)) higher than that of crystalline (10(-4) cm(2) V-1 s(-1)) and two orders higher than that of columnar rectangular phase (10(-5) cm(2) V-1 s(-1)), indicating a strong dependence of packing on bulk mobility.

Supramolecular P4VP-pentadecylphenol naphthatenebisimide comb-polymer: mesoscopic organization and charge transport properties - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A supramolecular comb polymer of pentadecyl phenol (PDP) substituted naphthalenebisimide (PDP-UNBI) with poly(4-vinylpyridine) (P4VP) is reported. The mesoscopic organization within the P4VP(PDP-UNBI), complexes was studied using wide-angle X-ray diffraction (WXRD) technicjues. The packing diagram obtained from the single-crystal XRD analysis of the PDP-UNBI crystals gave a clear picture of the initial arrangement present in self-associated PDP-UNBI alone. Correlating this with the XRD data of the hydrogen-bonded polymer complex provided insight into the probable packing of the P4VP chains within the crystalline lattice of PDP-UNBI leading to a highly ordered lamellar packing. Transmission electron microscopy (TEM) revealed the uniform mesomorphic lamellar structures in the domain range of similar to 5-10 nm. Furthermore, the charge carrier mobility measurements observed from space-charge-limited current (SCLC) measurements demonstrated that transport behaviour of the hydrogen-bonded P4VP(PDP-UNBI) complex (2 x 10(-2) cm(2) V-1 s(-1)) was comparable to that of the crystalline naphthalenebisimide molecule itself (9 x 10(-3) cm(2) V-1 s(-1)), which is a great achievement, since the complex now offers a package of solution-processable n-type semiconductor polymer with mobility equivalent to that of a small crystalline molecule.

Easy `filter-and-separate' method for enantioselective separation and chiral sensing of substrates using a biomimetic homochiral polymer - Senthilkumar, T.; Asha, S. K. (Chemical Communications, 2015)
We present a polyfluorene appended with protected L-glutamic acid that exhibited a reversible alpha-helix/beta-sheet-like conformation and helical porous fibrous morphology mimicking the super-structure of proteins. The new homochiral polymer probe enabled efficient heterogeneous enantioselective separation and chiral sensing of a wide variety of substrates from their aqueous racemic mixture using an easy `Filter-and-Separate' method.

Ionic conductivity probed in main chain liquid crystalline azobenzene polyesters - Nardele, Chinmay G.; Dhavale, Vishal M.; Sreekumar, K.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2015)
Three main chain thermotropic liquid crystalline (LC) azobenzene polymers were synthesized using the azobenzene twin molecule (P4P) having the structure Phenylazobenzene-tetraethyleneglycol-Phenylazobenzene as the AA monomer and diols like diethylene glycol, tetraethylene glycol (TEG), and hexaethylene glycol as the BB comonomer. Terminal C(O)OMe units on P4P facilitated transesterification with diols to form polyesters. All polymers exhibited stable smectic mesophases. One of the polymers, Poly(P4PTEG) was chosen to prepare composite polymer electrolytes with LiCF3SO3 and ionic conductivity was measured by ac impedance spectroscopy. The polymer/0.3 Li salt complex exhibited a maximum ionic conductivity in the range of 10(-5) S cm(-1) at room temperature (25 degrees C), which increased to 10(-4) S cm(-1) above 65 degrees C. The temperature dependence of ionic conductivity was compared with the phase transitions occurring in the sample and it was observed that the glass transition had a higher influence on the ionic conductivity compared to the ordered LC phase. Reversible ionic conductivity switching was observed upon irradiation of the polymer/0.3 Li salt complex with alternate UV and visible irradiation. (c) 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 629-641
Keywords: azo polymers; glass transition; liquid-crystalline polymers (LCP)

Selective and sensitive sensing of free bilirubin in human serum using water-soluble polyfluorene as fluorescent probe - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2015)
The adherence of serum protein on conjugated polymer is a major bottleneck in the application of the latter for selective sensing of small biomolecules in blood serum. In this report, we present new polyfluorenes with d-glucuronic acid appendage that is a nonreceptor for any serum protein, thereby providing a platform for selective sensing of free bilirubin in the clinically relevant range of <25 to >50 mu mol/L in human blood serum. The appended d-glucuronic acid formed noncovalent interactions with bilirubin, which in conjunction with favorable spectral overlap between the polymers and bilirubin facilitated efficient FRET process in aqueous solutions. Addition of bilirubin resulted in the quenching of the polyfluorene emission with simultaneous appearance of bilirubin emission exhibiting visual emission color change from blue to light green. The polymer remained stable in serum even under severe basic conditions and exhibited high selectivity with visual sensitivity only toward free bilirubin in human serum in the presence of crucial interferences such as hemoglobin, proteins, biliverdin, glucose, cholesterol, and metal ions. Nanomolar sensing of bilirubin could also be demonstrated successfully using one of the d-glucuronic acid appended polymer (PF-Ph-GlcA), which could sense similar to 150 nm of bilirubin in human serum. The combined role of energy transfer and noncovalent interaction highlights the potential of the new polymer design for highly selective sensing activity in complex biofluids.

Self-assembly directed template photopolymerization of perylenebisimide-poly (4-vinylpyridine): nano organization - Shinde, Shekhar; Asha, S. K. (Polymer, 2015)
A perylene bisimide derivative (PDP-UPBIAcry) having hydroxyl moieties at one termini and polymerizable acrylic units at the other termini was supramolecularly complexed with the pyridine units of Poly (4-vinyl pyridine) (P4VP), followed by photoinduced polymerization of the acrylic units to obtain lamellar organization in the <10 nm range. H-1 NMR studies including variable temperature (20 degrees C-70 degrees C) measurements were undertaken in DMSO-d(6) (anhydrous, extra dry) to understand the interaction between PDP-UPBIAcry and P4VP. The aromatic perylene protons of PDP-UPBIAcry registered an upfield chemical shift while the pyridine protons of P4VP exhibited small downfield shift in their 1:1 supramolecular complex. The hydrogen bonding interaction between pyridyl nitrogen and phenolic OH group was also traced in non-polar media like CDCl3 in model complexes of 4-vinyl pyridine (4VP) with PDP-UPBIAcry. Wide angle X-ray diffraction (WXRD) technique was used to study the bulk structure. Transmission electron microscopy (TEM) imaging revealed highly ordered layered assembly formed upon complexation. Observation from DFT energy minimization studies were correlated with X-ray diffraction data of the supramolecular complex [P4VP (PDP-UPBIAcry)](1.0) to understand the nature of packing of PDP-UPBIAcry that lead to the formation of highly ordered lamellar stacks alternating with P4VP. The higher ordering in the supramolecular polymer complex was also confirmed by the quenching of fluorescence and reduced fluorescence life times of thin solid films of the [P4VP Poly(PDP-UPBIAcry)](1.0) sample. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: hydrogen bonding; P4VP; Perylenebisimide

Fluorescent polystyrene microbeads as invisible security ink and optical vapor sensor for 4-nitrotoluene - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2016)
Color-tunable solid-state emitting polystyrene (PS) microbeads were developed by dispersion polymerization, which showed excellent fluorescent security ink characteristics along with sensitive detection of vapors of nitro aromatics like 4 nitro toluene (4-NT). The fluorophores pyrene and perylenebisimide were incorporated into the PS backbone as acrylate monomer and acrylate cross-linker, respectively. Solid state quantum yields of 94 and 20% were observed for the pyrene and perylenebisimide, respectively, in the PS/Py and PS/PBI polymers. The morphology and solid state fluorescence was measured by SEM, fluorescence microscopy, and absorbance and fluorescence spectroscopy techniques. The ethanol dispersion of the polymer could be used directly as a fluorescent security ``invisible'' ink, which became visible only under ultraviolet light. The color of the ink could be tuned depending on the amounts of the pyrene and perylenebisimide incorporated with blue and orange-green for pyrene alone or perylenebisimide alone beads respectively and various shades in between including pure white for beads incorporating both the fluorophores. More than 80% quenching of pyrene emission was observed upon exposure of the polymer in the form of powder or as spin-coated films to the vapors of 4-NT while the emission of perylenebisimide was unaffected. The limit of detection was estimated at 10(-5) moles (2.7 ppm) of 4-NT vapors. The ease of synthesis of the material along with its invisible ink characteristics and nitro aromatic vapor detection opens up new opportunities for exploring the application of these PS-based materials as optical sensors and fluorescent ink for security purposes.
Keywords: dispersion polymerization; invisible security ink; Perylenebisimide; pyrene; solid state detection

Improved all-polymer solar cell performance of n-type naphthalene diimide-bithiophene P(NDI2OD-T2) copolymer by incorporation of perylene diimide as coacceptor - Sharma, Sandeep; Kolhe, Nagesh B.; Gupta, Vinay; Bharti, Vishal; Sharma, Abhishek; Datt, Ram; Chand, Suresh; Asha, S. K. (Macromolecules, 2016)
Naphthalene diimide-bithiophene P(NDI2OD-T2) is a well-known donor-acceptor polymer, previously explored as n-type material in all-polymer solar cells (all-PSCs) and organic field effect transistor (OFETs) applications. The optical, bulk, electrochemical, and semiconducting properties of P(NDI2OD-T2) polymer were tuned via random incorporation of perylene diimide (PDI) as coacceptor with naphthalene diimide (NDI). Three random copolymers containing 2,2'-bithiophene as donor unit and varying compositions of naphthalene diimide (NDI) and perylene diimide (xPDI, x = 15, 30, and 50 mol % of PDI) as two mixed acceptors were synthesized by Stille coupling copolymerization. Proton NMR spectra recorded in CD Cl-3 showed that the pi-pi stacking induced aggregation among the naphthalene units could be successfully disrupted by the random incorporation of bulky PDI units. The newly synthesized random copolymers were investigated as electron acceptors in BHJ all-PSCs, and their performance was compared with P(NDI2OD-T2) as reference polymer. An enhanced PCE of 5.03% was observed for BHJ all-PSCs (all-polymer solar cells) fabricated using NDI-Th-PDI30 as acceptor and PTB7-Th as donor, while the reference polymer blend with the same donor polymer exhibited PCE of 2.97% efficiency under similar conditions. SCLC bulk carrier mobility measured for blend devices showed improved charge mobility compared to reference polymer, with PTB7-Th:NDI-Th-PDI30 blend device exhibiting the high hole and electron mobility of 4.2 x 10(-4) and 1.5 x 10(-4) cm(2)/(V s), respectively. This work demonstrates the importance of molecular design via random copolymer strategy to control the bulk crystallinity, compatibility, blend morphology, and solar cell performance of n-type copolymers.

Orientation effect induced selective chelation of Fe2+ to a glutamic acid appended conjugated polymer for sensing and live cell imaging - Senthilkumar, T.; Parekh, Nimisha; Nikama, Shrikant B.; Asha, S. K. (Journal of Materials Chemistry B, 2016)
Intracellular detection and imaging of labile iron(II) pools is very important in tracking physiological processes that demand new and rapid sensing probes. In this report, we present a water soluble polymer based probe for the fluorescence sensing and live cell imaging of labile Fe2+ ions with high selectivity for the first time. The polymer probe was based on conjugated polyfluorene which was appended with amino acid (L-glutamic acid). The biocompatibility of the polymer was confirmed from an MTT assay which demonstrated >90% cell viability even at 300 mu g ml(-1) loading of polymers. Simple glutamic acid did not show selectivity towards any of the divalent ions. However, glutamic acid appended polyfluorene exhibited selective chelation to Fe2+ ions resulting in immediate sensing activity for Fe2+ ions in water and living cells with fluorescence turn-off response. The limit of detection of the PF-Ph-GA polymer probe was 46 (+/- 2) nM which indicated high sensitivity for Fe2+ over other ions reported in the literature. The polymer also exhibited improved sensing activity in the range of intracellular pH (5-9) which is advantageous in differentiating endogenous changes. The probe was successfully applied for the fluorescence imaging of intracellular and supplemented labile iron(II) pools in living HeLa cells.

P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility - Saibal, B.; Chithiravel, Sundaresan; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Random donor-acceptor (D-A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN-OH) and Perylenebisimide (named UPBI-PDP), respectively, were complexed with Poly(4-vinyl pyridine) (P4VP). A series of random D-A supramolecular comb polymers were formed by varying the ratios of UPBI-PDP and OPVCN-OH with P4VP. A 100% P4VP-donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP-acceptor polymer complex [P4VP(UPBI1.00)] were also synthesized and characterized. Complex formation was confirmed by FT-IR and H-1 NMR spectroscopy. Solid state structural studies carried out using small angle X-ray scattering and wide angle X-ray diffraction experiments revealed altered packing of the D and A molecules in the complexes. Transmission electron microscopy images showed lamellar structures in the <10 nm scale for the P4VP(OPV1.00), P4VP(UPBI1.00), and mixed P4VP (D-A) complexes. The effect of the nanoscopic D-A self-assembly on the bulk mobility of the materials was probed using SCLC measurements. The mixed D-A random complexes exhibited ambipolar charge transport characteristics with higher values for the average bulk hole mobility estimate. P4VP(OPV0.25+UPBI0.75) exhibited an average hole mobility in the order of 10(-2) cm(2) V-1 s(-1) and electron mobility 10(-5) cm(2) V-1 s(-1). (C) 2016 Wiley Periodicals, Inc.
Keywords: donor-acceptor; oligo(phenylenevinylene); P4VP; Perylenebisimide; Self-assembly; structure-property relations; supramolecular comb polymer; supramolecular structures

Synthesis and structural characterization of twin liquid crystalline perylenebisimides - Prajitha, K. P.; Asha, S. K. (New Journal of Chemistry, 2016)
A series of twin perylenebisimide (PBI) molecules were synthesized and characterized having the structure PBI-(methylene spacer)-n-PBI where the length of the central polymethylene spacer segment was varied from n = 1 to 12. The PBI unit was imidized with an ethyl hexyl branched alkyl segment at the terminal and pentadecyl phenol at the other end which was linked through the polymethylene spacer to form the twin molecules. The differential packing afforded by the odd and even spacer central methylene segments resulted in an odd-even oscillation of the melting transitions as well as their enthalpies with higher values observed for the even twins. The odd-even oscillation was quite prominent for the spacers up to n < 7 after which it tapered off. PBI-T1 and PBI-T3 exhibited tendencies to form smectic liquid crystalline (LC) phases while most of the higher membered twin molecules exhibited tendencies for high temperature nematic phases. The ability to control the crystalline or mesogenic nature of the PBI molecules, which constitute an important member of the n type rylenebisimide family that finds application as electron transporters in field effect transistors (FETs) and organic solar cells, is promising as it provides a handle to design systems whose bulk packing is pre-defined to suit the requirements of the application.

Temperature sensitive emission color tuning and white light emission in segmented OPV polymer: perylene bisimide supramolecular complex - Shinde, Shekhar; Asha, S. K. (Macromolecules, 2016)
An oligo(phenylenevinylene) (OPV) based segmented polymer (POPV) and its small molecule model compound (SOPV) were designed with a carboxyl functionality in the side chain. The polymer and small molecule were complexed with pyridine functiorialized perylene bisimide (UPBIPy) and the properties of the donor: acceptor (D:A) complexes were compared. Both polymer and small molecule D:A complexes formed lamellar morphologies in the <10 nm length scale, which could be visualized by TEM and AFM imaging. The flexibility of the segmented polymer architecture imparted special properties to the polymer and its complex. The polymer complex (POPVC) exhibited white light emission with CIE color coordinates (0.27, 0.32) due to partial energy transfer from POPV to UPBIPy. The analogous model OPV complex (SOPVC) continued to show characteristic blue OPV emission in the complex also. The higher sensitivity of polymers toward temperature was made use of to tune the emission color in the complex from white (0.27, 0.32) at 30 degrees C to yellow-green (0.29, 0.31) at 100 degrees C and back to white (0.27, 0.31) upon cooling to 30 degrees C. Such a temperature sensitive emission color tuning was not observed in the small molecule complex under identical conditions.

Liquid crystalline supramolecular crosslinked polymer complexes of ditopic rylenebisimides and P4VP - Saibal, B.; Narayan, Rekha; Chithiravel, S.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Perylenebisimide and naphthalenebisimide (PBIPDP and NBI-PDP) end functionalized with pentadecyl phenol is designed as ditopic hydrogen bonding acceptors to form supramolecular crosslinked network with poly(4-vinyl pyridine) (P4VP). The pristine PBI-PDP has been grown as single crystals from DCM-MeOH (dichloromethane-methanol) mixture at room temperature, which revealed a P21 space group. Noticeably, the pentadecyl alkyl chain shields the aromatic perylene core on both sides resulting in the absence of p-p interaction in single-crystal assembly. The naphthalenebisimide derivative exhibits thermotropic liquid crystalline behavior, while both the molecules exhibits lyotropic liquid crystalline phases in tetrahydrofuran (THF), which were characterized using a combination of differential scanning calorimeter, X-ray diffraction, and polarized light microscopy. The hydrogen-bonded complex of both the rylenebisimides with P4VP preserves the mesomorphic properties in THF. The electron transport mobility measured by space charge limited current measurements reveals a two orders of magnitude increase in the charge transport in the P4VP complex compared to that of the pristine molecule. The average electron mobility obtained is mu(e, avg): 10(-3) cm(2)/Vs for P4VP-PBI compared to mu(e, avg): 10(-5) cm(2)/Vs for pristine PBI derivative. (C) 2017 Wiley Periodicals, Inc.
Keywords: crystal structures; ditopic rylenebisimide; hydrogen bonding; lyotropic liquid crystal; P4VP; Self-assembly; supramolecular crosslink; supramolecular structures

pi-Conjugated chromophore incorporated polystyrene nanobeads as single optical agent for three-channel fluorescent probe in bioimaging application - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Biomaterials Science & Engineering, 2017)
Fluorescent polystyrene (PS) nanobeads in the size range similar to 70-120 nm incorporating perylene bisimide (PBI-PS) and/or oligo(p-phenylenevinylene) (OPV-PS) was developed by miniemulsion polymerization technique. A dye loading content (DLC) of <3% was sufficient to impart high fluorescence emission capability to the PS beads. OPV-PS exhibited emission in the range 400-550 nm with peak emission at 450 nm (lambda(ex) = 350 nm; phi(FL) = 26%); PBI-PS showed emission from 520-650 nm with peak emission at 545 nm (lambda(ex) = 490 nm; phi(FL) = 9.7%) in 1x PBS buffer, whereas OPV(PBI)-PS nanobeads incorporating both the fluorophores exhibited multicolor emission capabilities (lambda(ex) from 350 to 490 nm). The nanoparticles were characterized by field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS) for size and zeta potential for surface charge. For bioimaging applications, the PS nanoparticles were incubated with HeLa cells. Cell viability analysis involving HeLa cells showed more than 90% cell viability confirming the biocompatibility of the PS The cellular uptake of the nanoparticles was confirmed by flow cytometry analysis and confocal laser scanning microscopy (CLSM) images. The subcellular localization of the nanoparticles in the cytoplasm could be precisely established by their simultaneous multicolor emission. The PS-based single optical agent presented here that can function as three-channel fluorescent probe to meet the requirements for multicolor bioimaging is advantageous.
Keywords: Biocompatibility; bioimaging

Probing cavity versus surface preference of fluorescent template molecules in molecularly imprinted polystyrene microspheres - Sonawane, Swapnil L.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Functional polystyrene (PS) crosslinked microbeads were developed by dispersion polymerization as fluorescent molecularly imprinted polymers (MIPs) having cavities with specific recognition sites. The functional azobenzene molecule modified with pyridine was self-assembled with Pyrenebutyric acid (template molecules), and introduced during the second stage of dispersion polymerization of polystyrene. The template molecule was removed from MIP by Soxhlet using acetonitrile as solvent. Non imprinted polymer (NIP) having no template was also synthesized for comparative study. Fluorescence spectroscopy could be used as a tool to derive insight into the location of the template molecules on the MIP or NIP. The template molecules were adsorbed on the surface of the NIPs during binding studies, which was evidenced from the pyrene excimeric emission observed at 440 nm. The template binding efficiency of the NIPs were much lower compared to MIPs. Pyrene emission from MIP upon rebinding showed typical monomeric emission in the 375-395 nm range, confirming its location in isolated cavities. In rebinding studies of the template molecules, the MIPs selectively took up the template for which the cavity was designed, which demonstrated their selectivity towards template molecules. (C) 2017 Wiley Periodicals, Inc.

Naphthalene diimide copolymers by direct arylation polycondensation as highly stable supercapacitor electrode materials - Sharma, Sandeep; Soni, Roby; Kurungot, Sreekumar; Asha, S. K. (Macromolecules, 2018)
Conjugated donor-acceptor copolymers based on naphthalene diimide (NDI) as acceptor and thiopheneterminated oligophenylenevinylene as donor moieties (P-1 and P-2, respectively) were synthesized using the direct (hetero) arylation (DHAP) polymerization route. Nitrile groups were introduced at the vinylene linkage in one copolymer (P-2) to fine-tune its electrochemical properties. Both polymers show) pi-pi* transition in the 300-480 nm region and intramolecular charge transfer (ICT) from thiophene to NDI in the 500-800 nm region in the absorption spectra. P-2 exhibits a blue-shifted intramolecular charge transfer (ICT) band in the absorption spectrum as well as a lower reduction potential in the cyclic voltammogram compared to the analogous polymer without the nitrile substitution (P-1). The two polymers were evaluated as type III supercapacitor materials by preparing composite electrodes with carbon nanotubes (CNTs) and employing 0.5 M H2SO4 as the electrolyte. Their performance was compared with that of P(NDI2OD-T2) as a reference polymer. The polymer P-2 based supercapacitor exhibits a specific capacitance of 124 F/g with excellent stability up to 5000 cycles with almost 100% retention of the initial capacitance in the potential window of -0.7 to 0.5 V. Compared to P-2, P-1 exhibits a specific capacitance of 84 F/g, while the corresponding value for the reference polymer P(NDI2OD-T2) is 61 F/g under identical conditions.

Designed amphiphilic polystyrene as surfactant for oligo(p-phenylenevinylene)-incorporated PS nanobeads and visual detection of bilirubin in human blood serum - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Applied Polymer Materials, 2019)
Amphiphilic polystyrene having pendant glucuronic acid (PS-DGlu) was designed and systematically synthesized to be used as a stabilizing agent in styrene miniemulsion polymerization, while covalently incorporating oligo(p-phenylenevinylene) (OPV)-based fluorophore to prepare PSG-OPV-n. This OPV fluorophore was incorporated with an aim to work as a signal transducer, while glucuronic acid on the surface of PS nanobeads would act as the water solubilizing moiety for PS to enable it to function as surfactant and also serve as an interaction site for free bilirubin to facilitate noncovalent interaction via hydrogen bonding. Efficient energy transfer from OPV to bilirubin was observed, owing to the appreciable spectral overlap between emission of OPV and absorption of bilirubin. Visual color change from blue to bluish green was observed under an UV lamp after the addition of bilirubin into the polymer. Selectivity of the sensor was checked among the pool of other interferences, such as glucose, sucrose, metal ions, cholesterol, and biliverdin. The limit of detection was found to be as low as 20 nM, which is far less than the clinical range for causing jaundice (<25 to >50 mu mol/L). Moreover, the developed sensor showed its effectiveness toward real time monitoring of free bilirubin in human serum.
Keywords: amphiphilic homopolymer; bilirubin; functionalized polystyrene nanobeads; oligo(p-phenylenevinylene); sensing

Rylene diimide-based alternate and random copolymers for flexible supercapacitor electrode materials with exceptional stability and high power density - Sharma, S.; Soni, R.; Kurungot, S.; Asha, S. K. (Journal of Physical Chemistry C, 2019)
Donor–acceptor pi-conjugated polymers are emerging as interesting electrode materials for supercapacitor device applications. They offer an exciting possibility of charge storage in both positive and negative electrodes because they are both p- and n-dopable. The ambipolar charging enables higher operating voltage, which can afford higher specific energy and power densities. The donor–acceptor design can be either donor-alternate-acceptor or donor-random-acceptor. This architectural variation has the potential to modify the charge storage; yet surprisingly not much literature data is available exploiting this aspect. This paper explores the alternate and random geometries of donor–acceptor π-conjugated polymers based on naphthalene diimide or perylene diimide (PDI) as the acceptor component and benzodithiophene (BDT) as the donor component and their application as composite electrode materials in a type III supercapacitor device. Results show that the donor–acceptor alternate design involving P(PDI-alt-BDT) is an excellent supercapacitor electrode material with specific capacitance of 113 F g–1 with excellent stability up to 4000 cycles and almost 100% retention of the initial capacitance in a single-electrode setup in a PC-LiClO4 organic electrolyte. A flexible supercapacitor device was also fabricated which shows areal capacitance of 35 mF cm–2 at a current density of 0.5 mA cm–2, which is promising for commercial applications.

Dual responsive cellulose microspheres with high solid-state fluorescence emission - Yadav, Prashant; Prajitha, K. P.; Dhaware, Vinita; Subramani, Mohan; Joy, Pattayil; Asha, S. K.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Materials that respond to multiple stimuli such as magnetic field and light are attractive for security and medical diagnostic applications. One of the major challenges in dual functional microspheres is that the presence of magnetic nanoparticles can quench fluorescence emission. Also, there is a probability of solid-state quenching due to the proximity of the fluorophore. We report here a facile approach to prepare cellulose microspheres with high solid-state fluorescence using 40 % tetrabutylammonium hydroxide (TBAH). The fluorescence quenching effect due to the presence of Fe3O4 nanoparticles and solid-state quenching due to aggregation of fluorophore was systematically investigated. Microspheres with the detectable magnetic response and fluorescence quantum yield as high as 0.57 (FMB 414) was obtained by optimizing the reaction conditions. Such a high quantum yield has not been reported before for dual stimuli-responsive fluorescent microspheres. The magnetic and fluorescent properties were found to be durable even after multiple washing cycles. These dual responsive cellulose microspheres can be added as security features to authenticate documents such as passports, degree certificates, currency notes, financial documents etc.
Keywords: Fluorescent; Magnetic; Microcrystalline cellulose; microspheres; Stimuli responsive microspheres; Tetrabutylammonium hydroxide

Enantioselective separation using chiral amino acid functionalized polyfluorene coated on mesoporous anodic aluminum oxide membranes - Nikam, Shrikant B.; Asha, S. K. (Analytical Chemistry, 2020)
Homochiral mesoporous anodic aluminum oxide membranes (AAO) were prepared by coating protected chiral D/L aspartic acid appended polyfluorene in the pores. These chiral AAO membranes successfully demonstrated enantioselective recognition and separation of a range of amino acids from their aqueous racemic mixture by simple filtration. Enantioselective separation was achieved by selective adsorption of one enantiomer from the aqueous racemic mixture into the chiral pores of the AAO membrane leaving the filtrate enriched with the other enantiomer. Extraction and quantification of the adsorbed amino acid (glutamic acid) demonstrated that 1 mg of homochiral polyfluorene could effectively extract about 3.5 mg of glutamic acid with 95% enantiomeric excess in 24 h. This is one of the highest enantiomeric excesses (ee %) and yields reported so far in the literature for a racemic mixture of glutamic acid. The pore size of the AAO membrane influenced the efficiency of separation with a reduction in pore size from 200 to 20 nm leading to reduced ee % (similar to 95% to similar to 28%). These results raise the possibility for a facile method to carry out enantioselective separation.

Self-assembly of bispentadecylphenol substituted perylenediimide with PS-b-P4VP for structure-property insight into the core of core-shell micelles - Roy, Moumita; Rajamohanan, Pattuparambil R.; Ravindranathan, Sapna; Asha, S. K. (ACS Applied Polymer Materials, 2020)
We report the use of a ditopic molecular probe bispentadecylphenol substituted perylenediimide (PBI-PDP) to examine the molecular level self-assembly of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in tetrahydrofuran (THF). A series of complexes were prepared between PS-b-P4VP copolymers with varying lengths of the 4-vinylpyridine chain and PBI-PDP. Light scattering and NMR spectroscopic studies reveal that the self-assembled structures of the solid complexes are not fully disrupted when the complexes are dissolved in THF. NMR experimental parameters measured for the small probe molecule provide detailed insights into the structure of the assemblies in solution as well as the interaction between the small molecule and the block copolymer. Such insights can have important implications in manipulating the nanostructure of block copolymer micelles to suit various application requirements. The dynamics and distribution of the PBI-PDP molecules within the assemblies in solution show a dependence on the length of the P4VP block. Transmission electron microscopy was employed to study the evolution of morphologies in films prepared from the self-assembled structures in THF solutions.
Keywords: core corona interface; ditopic molecular probe; environment; micelles; perylenediimide; PS-b-P4VP; Self-assembly

Enantioselective separation using chiral amino acid functionalized polyfluorene coated on mesoporous anodic aluminum oxide membranes (vol 92, pg 6850, 2020) - Nikam, Shrikant B.; Asha, S. K. (Analytical Chemistry, 2021)

High-voltage non-aqueous hybrid supercapacitor based on the N2200 polymer supported over multiwalled carbon nanotubes - Wavhal, Bhaiyyasaheb Anurath; Ghosh, Meena; Sharma, Sandeep; Kurungot, Sreekumar; Asha, S. K. (Nanoscale, 2021)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, is a widely accepted non-fullerene acceptor polymer that is used prominently in the energy harvesting application due to its ease of synthesis, high electron mobility, and other desirable semiconducting properties. With its recent foray into energy storage applications, there is tremendous potential for developing composites of N2200 with carbon nanotubes (CNTs) to improve its electrical properties and extend its applicability. Here we report a facile synthesis of an N2200 composite with multiwalled carbon nanotubes (MWCNTs) following an in situ approach to include MWCNTs into the polymer matrix, improving its electrochemical performance in an organic electrolyte (1 M LiClO4/propylene carbonate). The composite material with an optimum MWCNT content exhibits prominent redox behavior delivering a specific capacity of 80 mA h g((polymer))(-1) in a standard three-electrode cell. Moreover, the N2200/MWCNT composite material showing a battery-type electrochemical signature could perform as an efficient negative electrode in a high-voltage (2.4 V) hybrid supercapacitor device comprising capacitive activated carbon as the positive electrode.

Biodegradable, solvent-free photocrosslinkable PLLA resin formulations for additive manufacturing - Pal, Shibam; Asha, S. K. (Macromolecular Chemistry and Physics, 2022)
Acrylate end-functionalized linear and star poly l-lactide (PLLA) based aliphatic, photocurable oligomeric crosslinkers are developed, which are formulated with hydroxyl (ethyl)methacrylate (HEMA) as a biodegradable reactive diluent to demonstrate successful application for solvent-less 3D printing using digital light processing (DLP) technique as well as a custom-designed direct ink writing 3D printer. The resin formulation for 3D printing is optimized using spot curing, photodifferential scanning calorimetry and cure depth analysis. The 3D printed parts exhibit promising mechanical property along with improved hydrophilicity and biodegradability. The development of new photocurable resin formulations are expected to meet the growing demand for raw materials that can be applied for developing custom designed bio implantable objects.
Keywords: 3D printing; biodegradable materials; digital light processing; L-Lactide; photocurable materials

Direct (hetero)arylation (DHAP) polymerization of conjugated polymers - new A-B-A monomer design for P(NDI2OD-T2) & the challenges of adopting DHAP for continuous flow processes - Kakde, Navnath R.; Bharathkumar, H. J.; Wavhal, Bhaiyyasaheb A.; Nikam, Arun; Patil, Suneha; Dash, Soumya Ranjan; Vanka, Kumar; Krishnamoorthy, K.; Kulkarni, Amol; Asha, S. K. (Journal of Materials Chemistry C, 2022)
P(NDI2OD-T2), also known as Polyera ActivInk N2200, was synthesized by the atom-economic direct hetero arylation polymerization (DHAP) route using a newly designed A-B-A monomer. The new monomer design involved flanking naphthalene diimide with bithiophene units in the bay position, which was further polymerized with bay substituted 1,4-dibromo naphthalene diimide, to afford the same polymer structure as P(NDI2OD-T2). The new monomer design resulted in a very high molecular weight (M-n: 99.5 kDa, D-M: 2.8) defect-free polymer in a quantitative yield by the DHAP batch process using 1,2,4-trichlorobenzene (TCB) as the solvent. DFT studies revealed that the abstraction of the alpha-proton from the naphthalene diimide substituted 2,2 `-bithiophene was favorable by 2.6 kcal mol(-1) (Delta Delta G) as compared to that from 2,2 `-bithiophene. The reason for this improved C-H activation at the alpha position can be attributed to the presence of C-HMIDLINE HORIZONTAL ELLIPSIS pi stabilizing interactions in naphthalene diimide substituted 2,2 `-bithiophene, which strengthens upon the extended charge delocalization throughout the ring, thus stabilizing the conjugate base generated after the proton abstraction. Continuous flow polymerization was carried out by pumping the DHAP reaction mixture including the monomers, catalyst, and additive (pivalic acid) solubilized in degassed TCB through a pre-heated glass condenser packed with K2CO3 and Celite under aerobic conditions. Reproducible molecular weights of M-n: 29.5 kDa, D-M: 1.7 were obtained at much lower concentrations of reactant mixture compared to that for batch polymerization. This is the first report of the synthesis of P(NDI2OD-T2) by a Continuous Flow Process adopting the DHAP route to obtain a defect-free polymer with reasonable molecular weights. P(NDI2OD-T2) was also synthesized by Stille polymerization as a reference control sample to compare the thermal and charge carrier transport properties of the DHAP polymers. Organic field-effect (OFET) mobility measurements indicated mobility values in the order of 10(-3) cm(2) V-1 s(-1) for the DHAP batch polymer (using the novel monomer design). The P(NDI2OD-T2) synthesized by DHAP batch using the commonly used starting materials - bisbromo naphthalene diimide and bithiophene, exhibited OFET mobilities which were one order less, similar to 10(-4) cm(2) V-1 s(-1). This observation highlights the importance of structural design in the monomer to enhance reactivity and thereby the bulk properties using the DHAP route.

Structure-property insights into chiral thiophene copolymers by direct heteroarylation polymerization - Nikam, Shrikant B.; Singh, Chandrodai Pratap; Krishnamurty, Sailaja; Asha, S. K. (European Polymer Journal, 2022)
Chiral thiophene copolymers with fluorene as co monomer are designed having N-Boc-L-glutamic acid-1-tert-butyl ester as a chiral substituent located either on the thiophene unit or the fluorene unit with varying spacer length. The atom-economic direct heteroarylation polymerization (DHAP) method is utilized for the polymerization. Gibb's free energy (delta G) for polymerization determined using DFT calculations indicate difficulty in achieving high molar mass when the bulky chiral substituents are attached through short spacer to the backbone. The experimental observations are in agreement with the theoretical calculations with no polymer-ization or very low molar mass sticky compounds obtained for reactions with predicted + & UDelta;G values. Structure -property relationship are compared for two chiral polymers -P4 and P5 having the chiral substitution on thiophene and fluorene units respectively. No CD signal is observed in THF-a good solvent where the polymers are molecularly dissolved. Intense bisignated CD signal is observed for both polymers upon addition of methanol - a poor solvent, to their THF solution. The bisignate CD signal with maxima at lower wavelength and inflection point associated with the pi-pi* absorption band is characteristic of exciton coupling between polymer chains in a left handed helical orientation. Small differences are observed in the intensity of the CD signal for the polymers P4 and P5 highlighting the impact of steric hindrance of bulky pendant groups on polymer conformation. DHAP is an atom economic polymerization procedure that can be gainfully utilized for developing chiral conjugated polymers.
Keywords: chiral; DFT; Direct heteroarylation polymerization; Gibb?s free energy; Steric Hindrance

Design and synthesis of photocrosslinker and light blocker based on L-Amino acid polyester and their application in solvent-free resin formulation for DLP/SLA 3D printing - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Asha, S. K. (Polymers, 2023)
Customising material design for new technological applications like additive manufacturing (AM) is a challenging yet promising approach to create a palette of materials suitable for developing eco-friendly products. LGlutamic acid and L-aspartic acid based aliphatic, photocurable polyester crosslinkers were designed and developed and incorporated into a solvent-free photocurable resin formulation with hydroxyl (ethyl)methacrylate (HEMA). Proof-of-concept 3D printing of clear and transparent objects was demonstrated using digital light processing (DLP) and Stereolithography (SLA) techniques. Resolution of the 3D printed objects could be improved by incorporating a Dansyl labelled L-glutamic acid polyester, which not only aided in modulating the viscosity of the resin formulation but could also function as a light blocker, thereby avoiding polymerization of unwanted areas while 3D printing. The curing kinetics of the photocurable formulation was analyzed using photo differential Scanning Calorimetry. Enzymatic degradability studies of 3D printed films were undertaken in PBS buffer containing esterase enzyme and compared with 3D printed samples using HEMA and a commercial crosslinker (Trimethylolpropane triacrylate (TMPTA)). Scanning electron microscopy (SEM) was used to evaluate the morphology of the 3D printed films before and after enzymatic degradation in the PBS buffer for 60 days. The 3D printed amino acid crosslinked films of HEMA presented high degree of degradation in contrast to the near total absence of any degradation in the 3D printed film crosslinked using TMPTA. The availability of new photocurable formulations that are enzymatically degradable are highly sought after for 3D printing applications.
Keywords: 3D printing; Crosslinker; L -Amino acid Polyester; Light blocker; Photocurable

Exploring SiliaCat Pd-DPP as a recyclable heterogeneous catalyst for the multi-batch direct heteroarylation polymerization for P(NDI2OD-T2) - Kakde, Navnath R.; Asha, S. K. (Polymer Chemistry, 2023)
Donor-acceptor (D-A) conjugated polymers like P(NDI2OD-T2) are important constituents of the active layer of energy conversion devices like all-polymer solar cells. A cost-effective and environmentally amiable pathway for the synthesis of this and similar D-A polymers is highly desirable for the large-scale production of these materials. In this report we have combined two cost-effective approaches, namely, direct heteroarylation polymerization (DHAP) and a recyclable heterogeneous catalyst (SiliaCat Pd-DPP), for the multi-batch synthesis of P(NDI2OD-T2). The general applicability of the approach was first established with a series of conjugated small molecules based on naphthalene diimide and bithiophene derivatives (N1 to N6). The Meitlis hot filtration test and inductively coupled plasma-optical emission spectroscopy (ICP-OES) were conducted to estimate the quantity of leached palladium in the final reaction product. Catalyst recyclability up to five cycles was demonstrated for N1 with <2 ppm leached palladium impurity. A comparison was made with the homogeneous catalyst Pd(2)dba(3) which indicated the presence of much higher levels of palladium impurity in the final product. The polymerization of P(NDI2OD-T2) was demonstrated using the regular monomers (NDIOD-Br-2 and bithiophene) and also using a modified monomer with activated bithiophene (naphthalene diimide substituted bithiophene) under DHAP conditions employing SiliaCat Pd-DPP as the recyclable heterogeneous catalyst. The modified monomer proved to be amenable to DHAP polymerization using SiliaCat Pd-DPP as the heterogeneous catalyst, which could be consecutively reused four times with reproducible molecular weights in the range of M-n/M-w: 27.1/49.0 to 33.5/61.3.

Biocompatible PVAc-g--PLLA acrylate polymers for DLP 3D printing with tunable mechanical properties - Pal, Shibam; Gavhane, Utreshwar Arjun; Asha, S. K. (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: acid; copolymers; polymerization; TACONIC ANHYDRIDE

High-voltage symmetric supercapacitor electrodes via in situ synthesized multiwalled carbon nanotube-doped perylenebisimide-based donor-acceptor conjugate polymer P(PDI2OD-T2) - Wavhal, Aryan Anurath; Dilwale, Swati; Puthiyaveetil, Priyanka Pandinhare; Kakde, Navnath R.; Prakash, Medha; Kurungot, Sreekumar; Asha, S. K. (Journal of Physical Chemistry C, 2024)
This study presents the design and synthesis of a donor-acceptor pi-conjugated polymer composite P(PDI2OD-T2)/MWCNT tailored for high-voltage symmetric supercapacitor applications. The synthesis of P(PDI2OD-T2)/MWCNT was expedited by adopting a novel in situ polymerization technique that modifies the traditional Stille polymerization process. Incorporating approximately 33% by weight of multiwalled carbon nanotubes (MWCNT) into the polymer matrix, referred to as P-2, significantly enhances its conductivity, surface area, and porosity. These improvements in the material properties contribute to the superior electrochemical performance of the composites by promoting efficient electrolyte ion transport across the electrode-electrolyte interfaces. The symmetric supercapacitor devices fabricated with P-2 electrodes employing both liquid organic (LE-P-2||P-2) and quasi-solid-state gel (QSS- P-2||P-2) electrolytes demonstrate capacitance values of 85.4 and 84.2 F g(-1), respectively, at a current density of 0.25 A g(-1), while operating at a high-voltage window of 3.1 V. Moreover, these devices exhibit robust cycling stability, maintaining approximately 70% of their initial capacitance over 45,000 cycles with a coulombic efficiency of 96%. The successful demonstration of a quasi-solid-state symmetric supercapacitor underscores the potential of flexible energy storage solutions, as evidenced by a PMMA LiClO4 gel electrolyte prototype. This flexible device not only maintains structural integrity but also achieves an impressive power density of 18,600 W kg(-1) and an energy density of 112.4 Wh kg(-1), indicating its practical viability for real-world applications.

Room temperature photocurable PEEK polymer formulations for high-performance 3D printing applications - Pal, Shibam; Gaikwad, Yogesh; Asha, S. K. (ACS Applied Engineering Materials, 2024)
Digital light processing (DLP) technology was employed to 3D print acrylate-modified poly(ether ether ketone) (PEEK). PEEK and modified PEEK (mPEEK incorporating pendant pentadecyl chain) polymers were synthesized and end-capped with urethane acrylate units. These end-modified PEEK polymers were combined with commercially available (meth)acrylic cross-linkers and photoinitiator to create photocurable resin formulations suitable for DLP 3D printing. The resulting 3D-printed parts exhibited remarkable mechanical strength, with a Young’s modulus of 2.1 GPa. This surpassed the mechanical properties of commercial acrylate resin 3D-printed parts and achieved approximately 55% of the Young’s modulus of reported commercial PEEK polymer. Notably, the thermal properties of the 3D-printed materials were impressive, including a high glass transition temperature of 140 °C and stability with only around 10% weight degradation occurring at approximately 400 °C. These innovative resins demonstrated excellent printability with high resolution, enabling the fabrication of intricate shapes, including complex dental materials by DLP 3D printing. Their versatility extends to potential applications in dentistry, automobile manufacturing, and robotics.

Thiol-ene-based degradable 3D printed network from bio resource derived monomers ethyl-lactate and isosorbide - Pal, Shibam; Asha, S. K. (European Polymer Journal, 2024)
A polymeric ene-based thiol-ene network is reported that was demonstrated for light-based 3D printing. Allyl poly (acrylate ethyl lactate) (PAEL) was synthesized starting from ethyl lactate in an efficient and scalable manner. Ethyl lactate is a biobased material obtained naturally or chemically in high yields in the form of ethyl ester of lactic acid. Isosorbide, which is also a bio based resource was converted into thiol derivative and was used along with Pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) as multifunctional thiol. The polymeric nature of the ene (i.e. PAEL) imparted exceptionally high mechanical properties like Young's modulus of 1.75 GPa as well as high thermal stability with a decomposition temperature (Td,10%) exceeding 350 C for all the networks studied. The properties could also be customized by fine tuning the type and stoichiometric ratio of the thiol crosslinked employed. For instance, the Young's modulus range from 1.75 GPa to 1.03 GPa and glass transition temperature range from 44 C to 54 C could be achieved. DLP 3D printing was used to demonstrate the printability of the resins with high resolution and structural fidelity. The study also highlights the basemediated rapid hydrolytic degradation efficiency of the 3D printed parts, demonstrating the applicability of these novel polymeric ene based thiol-ene for sustainable and eco-friendly 3D printable formulations.
Keywords: 3D printing; Degradation; digital light processing; Poly (acrylate ethyl lactate); Thiol-ene

Carbohydrate-based polyester and amino acid polyester photocrosslinker and their resin formulation for 3D printing applications - Kamble, Ganesh N.; Joshi, Dheeraj Chandra; Gavhane, Utreshwar A.; Asha, S. K. (Chemistry-An Asian Journal, 2025)
Fully bio-based polyester was designed and synthesized using the carbohydrate-based diol 2,4:3,5-di-O-methylene-D-mannitol (Manx) and dimethyl ester of 2,3:4,5-di-O-methylene-galactaric acid (Galx). Photocurable resin formulations were prepared by incorporating up to 15 wt% of the carbohydrate polyester into hydroxyl ethyl methacrylate (HEMA) along with polyacrylamide crosslinker derived from L-glutamic acid. Complex 3D structures with good shape fidelity could be 3D printed using these novel polyester resin formulations. The incorporation of the carbohydrate polyester improved the glass transition temperature of the 3D-printed objects. Enzymatic erosion studies conducted using esterase enzyme revealed a higher degradation rate for the 3D-printed films containing the carbohydrate polyester. The hydrolytic degradation analysis conducted in both acidic and basic environments revealed that the 3D-printed polymer network exhibits stability and resilience in acidic conditions, while it undergoes complete degradation in basic conditions. This finding underscores the possibility of tailoring degradation processes under regulated circumstances.
Keywords: 3D printing; Amino acid; Carbohydrate polyester; Enzymatic degradation; Resin formulation

Recyclable l-glutamic acid-based polyester schiff base cross-linker for 3D printing applications - Kamble, Ganesh N.; Ghute, Aaditi P.; Asha, S. K. (ACS Applied Polymer Materials, 2026)
An l-amino acid-based polyester Schiff base cross-linker was developed from amine-functionalized polyester and biobased methacrylate vanillin. Vanillin, one of the few biobased and aromatic compounds readily available on an industrial scale, has recently garnered significant attention from the polymer community. The l-amino acid-based polyester Schiff base cross-linker (P3) was synthesized by condensing the aldehyde group of methacrylate vanillin with the amine group of the l-glutamic acid polyester. This polymeric cross-linker was used in resin formulations consisting of isobornyl acrylate as a reactive diluent and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide as the photoinitiator for digital light processing (DLP) three-dimensional (3D) printing. The resulting 3D-printed parts exhibited good mechanical properties, with a Young's modulus of 1.5 GPa, and high thermal stability, with a T max of 410 degrees C. The chemical degradability of the 3D-printed materials was demonstrated in a mixture of tetrahydrofuran and diethylene triamine (1:1) at 80 degrees C for 48 h. The reusability of the recovered resin was demonstrated by adding fresh methacrylate vanillin and photoinitiator, followed by 3D printing using a DLP 3D printer. The 3D-printed parts produced from the recycled resin retained substantial mechanical properties, with a Young's modulus of 1.39 GPa, and thermal stability, with a T max of 390 degrees C.
Keywords: 3D printing; chemical degradation; covalent adaptable network; l-glutamicacid; Vanillin

Vanillin-based recyclable thermosets and their glass fiber reinforced composites - Veetil, Ashwani Puthiya; Ravikumar, Aniruddha; Rajput, Tejas; Singh, Aman Kumar; Thakur, Tamanna; Krishna, Abhijith; Pol, Harshawardhan; Shanmuganathan, Kadhiravan; Asha, S. K. (Macromolecular Chemistry and Physics, 2026)
The accumulation of end-of-life plastic materials and composite reinforcement waste materials has brought much attention to developing sustainable alternatives and their re-processability. Incorporating covalent adaptable networks (CANs) into the crosslinked network bridges the concept of reversibility into the otherwise conventional non-reversible networks. This study investigates the structure-property relation in two reversible hardener systems derived from vanillin using Schiff base chemistry. The ``CAN'' systems were synthesized by condensation of vanillin with two amines, 4,4'-oxydianiline and tris(2-aminoethyl)amine, respectively, to form Va_ODA and Va_TAEA. The epoxy thermosets exhibited glass transition temperatures (T-g) of 125 degrees C and 115 degrees C, respectively, for Va_ODA and Va_TAEA, which is superior to most reversible vanillin-based systems reported. The vitrimer-thermosets exhibited promising mechanical and thermal properties, and reshaping abilities as a function of applied temperatures, indicating the dynamic nature of linkages. Chemical degradability was demonstrated by heating to 80 degrees C for 12 h in aqueous acidic medium or excess amine. The fabricated glass fiber composites exhibited good mechanical properties with tensile strength of 361 MPa and degradability in acetic acid/water mixture with a fiber recovery of >98 %. The recovered glass fiber exhibited almost similar tensile strength as the virgin glass fiber, demonstrating its potential reusability. The epoxy vitrimers underwent mechanical reprocessing through hot-pressing, as well as chemical reprocessing via 3D printing and by regeneration of imine bonds to form an epoxy resin.
Keywords: 3D printing; covalent adaptable network; re-processability; Schiff base; Vanillin